Toner and image forming method

By using charged control resins with different functional groups and polar resins with specific acid values ​​in the toner, the problem of release agent leakage in high temperature and high humidity environment is solved. When using ink cartridges with a large amount of toner filling in low temperature and low humidity environment, printing defects and toner residues are reduced, and more efficient printing quality is achieved.

CN119856121APending Publication Date: 2025-04-18ZEON CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380058860.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-31
Filing Date
2023-08-28
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The conventional toner is prone to seeping out of the release agent in a high temperature and high humidity environment, resulting in poor printing. When using ink cartridges with a large toner filling amount in a low temperature and low humidity environment, poor printing and increased toner residue are prone to occur.

Method used

Two positively charged control resins with different functional groups and polar resins with specific acid values ​​are used to form colored resin particles to inhibit the leakage of release agents, and to maintain an appropriate charged amount in the toner stored in a high temperature and high humidity environment for a long time to prevent poor printing.

Benefits of technology

The leakage of the release agent in a high temperature and high humidity environment is effectively suppressed, and the printing quality is improved when using ink cartridges with a large amount of toner filling, and the toner residue is reduced and the printing quality is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention provides a toner which is not liable to cause bleeding of a release agent even in a high-temperature and high-humidity environment and is not liable to cause poor printing even if the toner is stored for a long time in the high-temperature and high-humidity environment. According to the present invention, continuous printing can be performed while suppressing the occurrence of printing defects in both a low-temperature, low-humidity environment and a high-temperature, high-humidity environment, and variations in charge amount accompanying changes in the environment are suppressed. A toner containing colored resin particles and an external additive, the colored resin particles containing a binder resin, a colorant, a positively charged charge control resin, and a release agent, the positively charged charge control resin containing a copolymer A and a copolymer B, the copolymer A contains a functional group-containing monomer unit at a ratio of 1.50 mass% to 6.00 mass%, the copolymer B contains a functional group-containing monomer unit at a ratio of 0.10 mass% to less than 1.50 mass%, and the colored resin particles further contain a polar resin having an acid value of 0.5 mgKOH / g to 8.0 mgKOH / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a toner for developing an electrostatic latent image in electrophotography, electrostatic recording, electrostatic printing, and the like, and an image forming method using the toner. Background Art

[0002] In image forming apparatuses such as electrophotographic apparatuses, electrostatic recording apparatuses, and electrostatic printing apparatuses, an electrostatic latent image formed on a photoreceptor is developed with a toner, the toner image is transferred to a transfer material such as paper, and then fixed by heating or the like, thereby forming a fixed image.

[0003] In the fixing process of the toner, it is usually necessary to heat the fixing roller to a temperature of 150°C or higher during fixing, which requires a large amount of electricity. With the increasing demand for reducing the energy consumption of image forming apparatuses and increasing the speed of printing, there is a demand for toners that can maintain a high fixing rate even at low fixing temperatures, that is, toners that have excellent low-temperature fixing properties.

[0004] On the other hand, a toner with improved low-temperature fixability may easily cause blocking when stored at high temperatures or for a long time, that is, the storage stability of the toner may be reduced. Therefore, there is a demand for the development of a toner with improved low-temperature fixability without impairing the storage stability.

[0005] As a colorant with an excellent balance between storage stability and low-temperature fixing properties, for example, Patent Document 1 discloses a colorant, in which the colorant comprises colored resin particles containing a binder resin, a colorant and a release agent, and an external additive, wherein the colored resin particles further contain a styrene-based thermoplastic elastomer, and as a release agent, a fatty acid ester compound having a number average molecular weight (Mn) of 500 or more and less than 2000 is contained in an amount of 2 to 20 parts by mass relative to 100 parts by mass of the binder resin.

[0006] Patent document 2 discloses a toner comprising colored resin particles including a binder resin, a colorant, a charge control agent and a release agent, wherein the colored resin particles further contain an additive having a polydiene structure having a solubility of 3 to 40 g / 100 g in styrene at a temperature of 40° C., and the number of crystal domains of the release agent having an aspect ratio in the range of 2 to 10 in the colored resin particles is within a specific range or the storage modulus G'(60) of the colored resin particles at 60° C. determined by dynamic viscoelasticity measurement is within a specific range.

[0007] Patent document 3 discloses a toner, which includes colored resin particles containing a binder resin, a colorant and a softener (release agent), and an external additive, wherein the colored resin particles further contain a copolymer as a fixing aid, and the copolymer is a copolymer of at least any one of acrylate and methacrylate and at least any one of acrylic acid and methacrylic acid, and the acid value of the copolymer is 0.5 to 7 mgKOH / g, the weight average molecular weight Mw is 6000 to 50000, and the glass transition temperature is 60 to 85°C.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2019 / 065868;

[0011] Patent document 2: International Publication No. 2020 / 045664;

[0012] Patent document 3: International Publication No. 2014 / 133032. Summary of the invention

[0013] Problem that the invention aims to solve

[0014] The toners disclosed in Patent Documents 1 to 3 all contain a release agent. The release agent improves the releasability of the toner from the fixing roller and is therefore effective in improving the low-temperature fixing property of the toner.

[0015] On the other hand, the release agent is sometimes easy to seep out, and the seeped release agent will contaminate printing components such as photoreceptors, thereby causing poor printing such as fog. Therefore, a toner is required in which the release agent is not easy to seep out. However, the higher the temperature and humidity of the storage environment of the toner, the faster the release agent compatible with the binder resin moves to the surface of the toner, and the easier it is for the release agent to seep out. The toners disclosed in Patent Documents 1 to 3 are difficult to fully suppress the seepage of the release agent in a high temperature and high humidity environment above 45°C. In addition, if the previous toner is stored in such a high temperature and high humidity environment, there is also the problem of easy occurrence of poor printing such as fog when printing with the stored toner.

[0016] Furthermore, in recent years, in order to reduce component costs, ink cartridges with a large amount of toner filling have been used more frequently. If the amount of toner filling is large, the toner will be subjected to mechanical stress for a longer period of time during continuous printing. Therefore, if an ink cartridge with a large amount of toner filling is used for continuous printing, the charge amount of the toner in the ink cartridge is reduced, causing poor printing, resulting in a problem of increasing the amount of unusable toner remaining.

[0017] The object of the present invention is to provide a colorant and an image forming method using the colorant, wherein the colorant is not prone to leakage of release agent even in a high temperature and high humidity environment, and is not prone to poor printing even when the colorant is stored for a long time in a high temperature and high humidity environment. Even when using an ink cartridge filled with a large amount of colorant, continuous printing can be performed in both a low temperature and low humidity environment and a high temperature and high humidity environment, while suppressing the occurrence of poor printing until the residual colorant amount becomes less, thereby suppressing the change in charge amount associated with changes in temperature and humidity.

[0018] Solutions for solving problems

[0019] The inventors of the present invention have conducted in-depth research to solve the above-mentioned problems, and found that by using two positively charged charge control resins with different amounts of functional groups and a polar resin with a specific acid value, the leakage of the release agent in the colorant can be suppressed even in a high temperature and high humidity environment, and poor printing can be suppressed after the colorant is stored for a long time in a high temperature and high humidity environment, or in a low temperature and low humidity environment and a high temperature and high humidity environment, thereby suppressing the change in the charge amount of the colorant caused by environmental changes.

[0020] That is, the present invention provides a toner comprising colored resin particles and an external additive, wherein the colored resin particles contain a binder resin, a colorant, a positively charged charge control resin, and a release agent.

[0021] The positively charged charge control resin comprises a copolymer A and a copolymer B, wherein the copolymer A comprises a functional group-containing monomer unit at a ratio of 1.50 mass % to 6.00 mass %, and the copolymer B comprises a functional group-containing monomer unit at a ratio of 0.10 mass % to less than 1.50 mass %.

[0022] The colored resin particles further contain a polar resin having an acid value of 0.5 mgKOH / g or more and 8.0 mgKOH / g or less.

[0023] In addition, the present invention provides a toner comprising colored resin particles and an external additive, wherein the colored resin particles contain a binder resin, a colorant, a positively charged charge control resin, and a release agent.

[0024] The positively charged charge control resin comprises a copolymer A and a copolymer B, wherein the copolymer A comprises a functional group-containing monomer unit at a ratio of 1.50 mass % to 6.00 mass %, and the copolymer B comprises a functional group-containing monomer unit at a ratio of 0.10 mass % to less than 1.50 mass %.

[0025] The colored resin particles further contain a polar resin having an acid value of 0.5 mgKOH / g or more and 5.0 mgKOH / g or less.

[0026] In the colorant of the present invention, it is preferred that, in each copolymer contained as the above-mentioned positively charged charge control resin, when the proportion (mass %) of the functional group-containing monomer unit is F and the content (mass parts) of the copolymer relative to 100 mass parts of the above-mentioned binder resin is m, the sum of the products of F and m (F×m) calculated for the above-mentioned copolymers is greater than 2.00 and less than 6.00.

[0027] In the toner of the present invention, it is preferred that the acid value (mgKOH / g) of the polar resin is x, the content (parts by mass) of the polar resin relative to 100 parts by mass of the binder resin is m. P The ratio (mass %) of the functional group-containing monomer units in the copolymer A is F A , the content (mass parts) of the copolymer A relative to 100 parts by mass of the binder resin is m A When X and mp are equal (X×m P ) and F A and m A The product of (F A ×m A ) is the absolute value of the difference (|X×m P -F A ×m A |) is below 2.50.

[0028] The toner of the present invention preferably contains a fatty acid ester compound having a number average molecular weight (Mn) of 500 to less than 2000 as the release agent in an amount of 5 to 30 parts by mass based on 100 parts by mass of the binder resin.

[0029] In the toner of the present invention, it is preferred that the colored resin particles further contain a styrene-based thermoplastic elastomer in an amount of 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the binder resin.

[0030] The image forming method of the present invention is characterized by using the above-mentioned toner of the present invention.

[0031] Effects of the Invention

[0032] According to the present invention as described above, a toner is provided, which is not prone to leakage of a release agent even in a high temperature and high humidity environment, and is not prone to poor printing even when using a toner stored for a long time in a high temperature and high humidity environment. When using an ink cartridge filled with a large amount of toner, continuous printing can be performed in both a low temperature and low humidity environment and a high temperature and high humidity environment, while suppressing the occurrence of poor printing until the amount of toner remaining decreases, thereby suppressing the change in charge amount accompanying changes in temperature and humidity. In addition, by using the toner, an image forming method that is not prone to poor printing is provided. DETAILED DESCRIPTION

[0033] The toner of the present invention is characterized by comprising colored resin particles and an external additive, wherein the colored resin particles contain a binder resin, a colorant, a positively charged charge control resin, and a release agent.

[0034] The positively charged charge control resin comprises a copolymer A and a copolymer B, wherein the copolymer A comprises a functional group-containing monomer unit at a ratio of 1.50 mass % to 6.00 mass %, and the copolymer B comprises a functional group-containing monomer unit at a ratio of 0.10 mass % to less than 1.50 mass %.

[0035] The colored resin particles further contain a polar resin having an acid value of 0.5 mgKOH / g to 8.0 mgKOH / g, preferably a polar resin having an acid value of 0.5 mgKOH / g to 5.0 mgKOH / g.

[0036] The colorant of the present invention combines a copolymer A having a higher proportion of functional group-containing monomer units (sometimes referred to as "functional group amount" in the present invention) and a copolymer B having a lower functional group amount as a positively charged charge control resin in the colored resin particles, and further contains a polar resin having an acid value in the above-mentioned specific range, so that even in a high temperature and high humidity environment above 45°C, it is not easy for the release agent to bleed out. Even if the colorant is used and stored for a long time in such a high temperature and high humidity environment, printing defects such as fogging are not easy to occur. When using an ink cartridge filled with a large amount of colorant, continuous printing can be performed in both a low temperature and low humidity environment and a high temperature and high humidity environment, while suppressing the occurrence of printing defects until the residual amount of colorant becomes less, thereby suppressing the change in charge amount associated with changes in temperature and humidity.

[0037] The more functional groups in the copolymer containing functional groups used as the positively charged charge control resin, the stronger the charge imparting effect. On the other hand, the polar resin having an acid value plays a role in reducing the charge amount of the toner. This is because the acidic groups contained in the polar resin leak charge due to moisture absorption.

[0038] If the charge amount of the toner is too much, the transfer amount of the toner is insufficient, resulting in insufficient printing density. On the other hand, if the charge amount of the toner is too little, the electrostatic repulsion of the toner particles to the photoreceptor is reduced, and the toner particles are easily attached to the photoreceptor. If the toner particles adhere to the photoreceptor, it will cause fogging. In addition, the charge amount of the toner tends to increase in a low temperature and low humidity environment, and tends to decrease in a high temperature and high humidity environment.

[0039] Furthermore, in a toner containing a polar resin under a high temperature and high humidity environment, since the acidic group of the polar resin easily absorbs moisture, leakage of charges caused by the polar resin easily occurs, and thus the charge amount is easily reduced.

[0040] In contrast, the toner of the present invention has an appropriate charge amount by combining copolymers A and B containing functional groups in the above-mentioned specific range and a polar resin having an acid value in the above-mentioned specific range, so that poor printing such as insufficient printing concentration or fogging is not likely to occur in both low-temperature and low-humidity environments and high-temperature and high-humidity environments. In addition, the toner of the present invention is also easy to maintain an appropriate charge amount in the case of environmental changes or in the case of continuous printing. When continuous printing is performed using an ink cartridge filled with a large amount of toner, the toner is subjected to mechanical stress for a longer period of time, but since the toner of the present invention is easy to maintain an appropriate charge amount, when using an ink cartridge filled with a large amount of toner, continuous printing can be performed in both low-temperature and low-humidity environments and high-temperature and high-humidity environments, while suppressing the occurrence of poor printing until the amount of residual toner decreases.

[0041] Furthermore, since the acid value of the polar resin contained in the toner of the present invention is not too high, the toner of the present invention can suppress a decrease in charge amount even in a high temperature and high humidity environment, and the charge amount fluctuates less with changes in temperature and humidity.

[0042] Furthermore, the copolymer including a functional group and the polar resin having an acid value tend to be more preferentially present on the surface side of the colored resin particles as the amount of the functional group is larger or the acid value is higher.

[0043] It is inferred that the toner of the present invention contains copolymers A and B having functional group amounts within the above-specified range and a polar resin having an acid value within the above-specified range in combination, and that the above substances are preferentially present on the surface side of the colored resin particles, and a dense resin layer is formed on the surface of the colored resin particles, thereby suppressing the bleeding of the release agent even in a high temperature and high humidity environment of more than 45°C.

[0044] If a toner with release agent seepage is used for printing, fogging is likely to occur. If the release agent in the toner seeps out, the release agent moves from the toner to the limiting scraper or the like during printing, and the release agent attached to the limiting scraper or the like causes fogging. One of the reasons for fogging when the conventional toner is used for printing after being stored for a long time in a high temperature and high humidity environment may also be insufficient charge of the toner, but the impact caused by the release agent seeping out during storage is greater.

[0045] In contrast, the toner of the present invention is less likely to cause bleeding of the release agent even when stored for a long time in a high temperature and high humidity environment and has an appropriate charge amount. Therefore, even if the toner of the present invention is stored for a long time in a high temperature and high humidity environment, printing defects such as fogging are less likely to occur.

[0046] Hereinafter, a method for producing the colored resin particles contained in the toner of the present invention, the colored resin particles obtained by the production method, and the toner of the present invention are described in order.

[0047] In addition, in the present invention, "to" in a numerical range means that the numerical values ​​described before and after it are included as the lower limit and the upper limit.

[0048] 1. Method for producing colored resin particles

[0049] In general, the production methods of colored resin particles are roughly divided into dry methods such as pulverization methods, and wet methods such as emulsion polymerization coagulation methods, suspension polymerization methods, and dissolution suspension methods. Wet methods are preferred from the viewpoint of easily obtaining a toner having excellent printing characteristics such as image reproducibility. Among wet methods, polymerization methods such as emulsion polymerization coagulation methods and suspension polymerization methods are preferred from the viewpoint of easily obtaining a toner having a small particle size distribution at the micron level. Among the polymerization methods, suspension polymerization methods are more preferred.

[0050] The emulsion polymerization coagulation method is a method of polymerizing the emulsified polymerizable monomer to obtain a resin particle emulsion, and coagulating the colorant dispersion to produce colored resin particles. In addition, the dissolution suspension method is a method of forming droplets of a solution in which a binder resin, a colorant, and other toner components are dissolved or dispersed in an organic solvent in an aqueous medium, and removing the organic solvent to produce colored resin particles. Various known methods can be used.

[0051] The colored resin particles contained in the toner of the present invention can be produced by a wet method or a dry method. When the colored resin particles are produced by (A) suspension polymerization method which is preferred among wet methods or by (B) pulverization method which is a typical dry method, the following process is used.

[0052] (A) Suspension polymerization

[0053] (A-1) Preparation step of polymerizable monomer composition

[0054] First, a polymerizable monomer, a colorant, a positively charged charge control resin, a polar resin, a release agent, and other additives such as a styrene-based thermoplastic elastomer and a molecular weight modifier are mixed as needed to prepare a polymerizable monomer composition. Mixing when preparing the polymerizable monomer composition is performed using a disperser such as an inline emulsifying disperser or a medium emulsifying disperser.

[0055] (Polymerizable Monomer)

[0056] In the present invention, a polymerizable monomer refers to a monomer containing a functional group that can be polymerized, and the polymerizable monomer is polymerized to form a binder resin. As the main component of the polymerizable monomer, a monovinyl monomer is preferably used. As a monovinyl monomer, for example: styrene; styrene derivatives such as vinyl toluene and α-methylstyrene; acrylic acid and methacrylic acid; acrylates such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate and dimethylaminoethyl acrylate; methacrylates such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate and dimethylaminoethyl methacrylate; nitrile compounds such as acrylonitrile and methacrylonitrile; amide compounds such as acrylamide and methacrylamide; olefins such as ethylene, propylene and butene. These monovinyl monomers can be used alone or in combination of two or more. Among these, as a monovinyl monomer, styrene, styrene derivatives, and acrylates or methacrylates are preferably used. As the main component of the polymerizable monomer, it is particularly preferred to use at least one selected from styrene and styrene derivatives and at least one selected from acrylates and methacrylates. By using such a polymerizable monomer, colored resin particles containing a styrene acrylic resin as a binder resin can be obtained. In addition, the main component refers to a component containing a proportion of more than 50% by mass.

[0057] Styrene acrylic resin has negative charge. Regarding the toner containing a negatively charged binder resin, compared with the case of a negatively charged toner, when it is made into a positively charged toner, it is more susceptible to mechanical stress during continuous printing, which wears the surface of the colored resin particles, and thus it is more likely to cause a decrease in charge. In contrast, the toner of the present invention, which is a positively charged toner, is not prone to a decrease in charge caused by wear of the surface of the colored resin particles even if it contains a negatively charged binder resin. It can be inferred that this is because the toner of the present invention contains copolymers A and B, which are positively charged charge control resins with different functional group amounts, and has a distribution in which copolymer A tends to be present on the outer surface side of the colored resin particles and copolymer B tends to be present on the more central side of the colored resin particles, thereby the colored resin particles have excellent wear resistance.

[0058] In order to improve thermal excursion and improve storage properties, it is preferred to use any cross-linking polymerizable monomer together with the monovinyl monomer. A cross-linking polymerizable monomer refers to a monomer having two or more polymerizable functional groups. Examples of cross-linking polymerizable monomers include aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene and their derivatives; ester compounds in which alcohols having two or more hydroxyl groups such as ethylene glycol dimethacrylate and diethylene glycol dimethacrylate are ester-bonded with two or more carboxylic acids having carbon-carbon double bonds; other divinyl compounds such as N,N-divinylaniline and divinyl ether; compounds having three or more vinyl groups, etc. These cross-linking polymerizable monomers can be used alone or in combination of two or more.

[0059] In the present invention, the crosslinkable polymerizable monomer is usually used in a ratio of 0.1 to 5 parts by mass, preferably 0.3 to 2 parts by mass, based on 100 parts by mass of the monovinyl monomer.

[0060] Furthermore, it is preferred to use a macromonomer as a part of the polymerizable monomers because the balance between the storage stability and the low-temperature fixing property of the obtained toner becomes good.

[0061] As the macromonomer, for example, reactive oligomers and polymers having a carbon-carbon unsaturated double bond that can be polymerized at the end of the molecular chain and a number average molecular weight of generally 1000 to 30000 can be cited. As the above-mentioned macromonomer, for example, styrene macromonomer, styrene-acrylonitrile macromonomer, polyacrylate macromonomer and polymethacrylate macromonomer can be cited. In particular, at least one selected from polyacrylate macromonomers and polymethacrylate macromonomers can be preferably used. As the acrylic acid ester used for the polyacrylate macromonomer, for example, the same acrylic acid ester that can be used as the above-mentioned monovinyl monomer can be cited, and as the methacrylate used for the polymethacrylate macromonomer, for example, the same methacrylate that can be used as the above-mentioned monovinyl monomer can be cited. As the above-mentioned macromonomer, it is particularly preferred to appropriately select and use the following macromonomer: by containing it in the above-mentioned polymerizable monomer, the glass transition temperature (Tg) of the obtained adhesive resin becomes higher than that of the case where it is not contained.

[0062] As the macromonomer, a commercial product may be used. Examples of the commercial product of the macromonomer include macromonomer series AA-6, AS-6, AN-6S, AB-6, and AW-6S manufactured by Toagosei Co., Ltd.

[0063] The above-mentioned macromonomers can be used alone or in combination of two or more.

[0064] When the polymerizable monomer contains the macromonomer, the content of the macromonomer is not particularly limited, but is preferably 0.03 to 5 parts by mass, more preferably 0.05 to 1 part by mass, based on 100 parts by mass of the monovinyl monomer.

[0065] The content of the polymerizable monomer is not particularly limited, but is preferably 60 to 95 parts by mass, more preferably 65 to 90 parts by mass, and even more preferably 70 to 85 parts by mass based on 100 parts by mass of the total solid content of the polymerizable monomer composition.

[0066] In the present invention, the solid content refers to all components except the solvent, and the solid content also includes liquid monomers and the like.

[0067] (Colorant)

[0068] As the colorant, any colorant used in conventional toners can be appropriately selected and used without particular limitation. When a color toner is produced, a black, cyan, yellow, or magenta colorant can be used.

[0069] As the black colorant, for example, carbon black, titanium black, magnetic powder such as iron zinc oxide and iron nickel oxide, etc. can be used.

[0070] As cyan colorants, phthalocyanine pigments such as copper phthalocyanine pigments and their derivatives, cyan pigments such as anthraquinone pigments, and cyan dyes can be used. Specific examples include CI Pigment Blue 2, 3, 6, 15, 15:1, 15:2, 15:3, 15:4, 16, 17:1, 60; CI Solvent Blue 70, etc.

[0071] As yellow colorants, for example, azo pigments such as monoazo pigments and disazo pigments, yellow pigments such as condensed polycyclic pigments, and yellow dyes can be used. Specifically, for example, CI Pigment Yellow 3, 12, 13, 14, 15, 17, 62, 65, 73, 74, 83, 93, 97, 120, 138, 155, 180, 181, 185, 186, 213, 214; CI Solvent Yellow 98, 162, etc. can be used.

[0072] As the magenta colorant, for example, azo pigments such as monoazo pigments and disazo pigments; magenta pigments such as condensed polycyclic pigments such as quinacridone pigments; and magenta dyes can be used. Specifically, for example, CI Pigment Red 31, 48, 57:1, 58, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 149, 150, 163, 170, 184, 185, 187, 202, 206, 207, 209, 237, 238, 251, 254, 255, 269; CI Pigment Violet 19; CI Solvent Red 1, 3, 8, 23, 24 4, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28, etc.

[0073] The above colorants can be used alone or in combination of two or more.

[0074] The content of the colorant is not particularly limited, but is preferably 5 to 15 parts by mass, more preferably 7 to 13 parts by mass, relative to 100 parts by mass of the binder resin, from the viewpoint of obtaining a sufficient image density. In addition, the content of the colorant in the toner is preferably 5 to 15 parts by mass, more preferably 7 to 13 parts by mass, relative to 100 parts by mass of the binder resin.

[0075] In the present invention, 100 parts by mass of the binder resin is the same as 100 parts by mass of the polymerizable monomer used to obtain the binder resin, and in the case of core-shell type colored resin particles, is the same as 100 parts by mass of the polymerizable monomer used to obtain the core layer.

[0076] (Positively charged charge control resin)

[0077] As a positively chargeable charge control resin, copolymer A and copolymer B can be used in combination, wherein the copolymer A contains a functional group-containing monomer unit at a ratio of 1.50 mass % to 6.00 mass % and the copolymer B contains a functional group-containing monomer unit at a ratio of 0.10 mass % to less than 1.50 mass %.

[0078] In the above-mentioned copolymers A and B, the functional group-containing monomer unit refers to a monomer unit containing a functional group imparting positive chargeability.

[0079] From the viewpoint of improving the effect of suppressing the bleeding of the release agent, the functional group amount of the above-mentioned copolymer A is preferably 1.60 mass % or more, and more preferably 1.80 mass % or more. On the other hand, from the viewpoint of making the charge of the colorant easy to become appropriate, especially suppressing the reduction in printing concentration caused by the excessive charge of the colorant, it is preferably 4.00 mass % or less, and more preferably 3.00 mass % or less.

[0080] From the viewpoint of making the charge amount of the colorant easy to become appropriate, especially suppressing the generation of fog caused by too low charge amount of the colorant, the functional group amount of the above-mentioned copolymer B is preferably 0.40 mass % or more, more preferably 0.50 mass % or more. On the other hand, from the viewpoint of making the charge amount of the colorant easy to become appropriate, especially suppressing the reduction in printing concentration caused by too high charge amount of the colorant, it is preferably 1.40 mass % or less, more preferably 1.20 mass % or less.

[0081] As the above-mentioned copolymers A and B, copolymers containing monomer units containing functional groups that bring positive charge, aromatic vinyl monomer units and (meth) acrylic acid ester monomer units are preferred. Here, the aromatic vinyl monomer units and (meth) acrylic acid ester monomer units do not contain functional groups that bring positive charge. The above-mentioned copolymers have excellent compatibility with the binder resin, so the charge amount of the toner is easily uniform.

[0082] Furthermore, the copolymers A and B are preferably copolymers that are soluble in an aromatic vinyl monomer from the viewpoint of dispersibility in the polymerizable monomer composition.

[0083] In the present invention, (meth)acrylate refers to acrylate and methacrylate, respectively.

[0084] Examples of the functional group imparting positive chargeability include pyridinium groups, amino groups, quaternary ammonium groups, quaternary ammonium salt groups, etc. Quaternary ammonium salt groups are preferred because they can function effectively even in a non-magnetic one-component developer and the charge amount of the toner can be easily made uniform.

[0085] Quaternary ammonium salts have -NR3 + ·X - In the ionic structure, the three Rs are independently a hydrogen atom or a substituent such as an alkyl group, and a hydrogen atom or a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms is particularly preferred. - A halogen ion, an alkyl group in which one hydrogen atom is replaced by a halogen ion, or an alkyl group in which at least one hydrogen atom can be replaced by a halogen atom and has -SO3 - 、-PO3 - or -BO3 - The hydrocarbon group includes, for example, an alkyl group, an aromatic hydrocarbon group, and a substituted aromatic hydrocarbon group. From the viewpoint of being easy to maintain the charge amount of the toner during continuous printing and being less likely to cause printing defects, X - Particularly preferred are those having -SO3 in which at least one hydrogen atom may be substituted by a halogen atom. - The hydrocarbon group is preferably an aromatic sulfonic acid anion which may have at least one substituent selected from a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms and a halogen atom, and further preferably a benzenesulfonic acid anion or a p-toluenesulfonic acid anion.

[0086] The above-mentioned copolymers A and B may be, for example, copolymers obtained by copolymerizing a vinyl monomer containing a functional group imparting positive charge and other vinyl monomers copolymerizable therewith, or may be copolymers in which a functional group imparting positive charge is introduced by modification treatment after polymerization of a vinyl monomer not containing a functional group imparting positive charge.

[0087] The copolymers preferably used as the copolymers A and B and containing a monomer unit containing a quaternary ammonium salt group, an aromatic vinyl monomer unit, and a (meth)acrylic acid ester monomer unit are not particularly limited, and can be obtained, for example, by the following method.

[0088] The polymerization method is not limited thereto, and for example, a known polymerization method such as emulsion polymerization, dispersion polymerization, suspension polymerization, solution polymerization, etc. can be employed.

[0089] (i) A method in which an aromatic vinyl monomer, a (meth)acrylate monomer and an N,N-disubstituted aminoalkyl (meth)acrylate monomer are copolymerized in the presence of a polymerization initiator and then the amino group is quaternized using a quaternizing agent such as a halogenated organic compound or an acid ester compound.

[0090] (ii) A method of copolymerizing an aromatic vinyl monomer, a (meth)acrylate monomer, and a monomer obtained by quaternizing an N,N-disubstituted aminoalkyl (meth)acrylate monomer using a quaternizing agent such as a halogenated organic compound or an acid ester compound in the presence of a polymerization initiator.

[0091] As the above-mentioned aromatic vinyl monomer, for example, styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2-propylstyrene, 3-propylstyrene, 4-propylstyrene, 2-isopropylstyrene, 3-isopropylstyrene, 4-isopropylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-butylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 2-methyl-α-methylstyrene, 3-methyl-α-methylstyrene, 4-methyl-α-methylstyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, vinylnaphthalene, etc. can be mentioned. Among these, styrene and α-methylstyrene are preferred. These can be used alone or in combination of two or more.

[0092] As the above-mentioned (meth)acrylate monomer, it is preferred to use, for example, an alkyl (meth)acrylate monomer that may have a hydroxyl group. As the alkyl (meth)acrylate monomer that may have a hydroxyl group, for example, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hydroxypropyl (meth)acrylate, dodecyl (meth)acrylate, etc. can be cited. These can be used alone or in combination of two or more. In the above-mentioned alkyl (meth)acrylate monomer, the number of carbon atoms of the alkyl group is not particularly limited, preferably 1 to 12, more preferably 1 to 8, and further preferably 1 to 6. In addition, an alkyl (meth)acrylate monomer that does not have a substituent is particularly preferred.

[0093] As the above-mentioned N,N-disubstituted aminoalkyl (meth)acrylate monomer, for example, dimethylaminomethyl (meth)acrylate, diethylaminomethyl (meth)acrylate, dipropylaminomethyl (meth)acrylate, diisopropylaminomethyl (meth)acrylate, ethylmethylaminomethyl (meth)acrylate, methylpropylaminomethyl (meth)acrylate, dimethylamino-1-ethyl (meth)acrylate, diethylamino-1-ethyl (meth)acrylate, dipropylamino-1-ethyl (meth)acrylate, etc. can be mentioned. These can be used alone or in combination of two or more. In the N,N-disubstituted aminoalkyl (meth)acrylate monomer, the number of carbon atoms of the alkyl group is not particularly limited, and is preferably 1 to 3.

[0094] Examples of the halogenated organic compound used as the quaternizing agent include linear, branched or cyclic alkyl halides having 1 to 6 carbon atoms such as methyl chloride, dichloromethane and chloroform; and aromatic halides such as chlorobenzene, 4-chlorotoluene and 1-chloronaphthalene.

[0095] Examples of the acid ester compound used as the quaternizing agent include alkyl alkyl sulfonates such as methyl methanesulfonate and ethyl methanesulfonate; alkyl benzenesulfonates such as methyl benzenesulfonate; alkyl p-toluenesulfonates such as methyl p-toluenesulfonate; phosphoric acid esters such as trimethyl phosphate; and boric acid esters such as trimethyl borate.

[0096] These quaternizing agents can be used alone or in combination of two or more.

[0097] The monomer unit containing a quaternary ammonium salt group contained in the copolymer is preferably a structural unit represented by the following formula [I].

[0098] [Chemical formula 1]

[0099]

[0100] [In the above formula [I], R 1 is a hydrogen atom or a methyl group, R 2 is a linear or branched alkylene group having 1 to 3 carbon atoms in which at least one hydrogen atom may be substituted by a halogen atom, R 3 ~R 5 are each independently a hydrogen atom, or a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms, - Benzene or naphthalene having any one of -SO3-, -PO3- or -BO3-, which is a halogen ion or may have at least one substituent selected from a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms and a halogen atom.]

[0101] X -Benzene or naphthalene having any one of -SO3-, -PO3- or -BO3-, which is a halogen ion, or which may have at least one substituent selected from a linear, branched or cyclic alkyl group having 1 to 6 carbon atoms and a halogen atom. From the viewpoint of being easy to maintain the charge of the toner during continuous printing and being less likely to cause printing defects, X - More preferred are the above-mentioned aromatic sulfonic acid anions which may have a substituent. Examples of the above-mentioned aromatic sulfonic acid anions include benzenesulfonic acid anions and p-toluenesulfonic acid anions.

[0102] Specific examples of the structural unit represented by the formula [I] include structural units corresponding to quaternary ammonium salt group-containing monomers such as N,N-diethyl-N-methyl-2-(methacryloyloxy)ethyl ammonium chloride, 2-(methacryloyloxy)ethyltrimethylammonium chloride (DMC; dimethylaminoethyl methyl methacrylate chloride), 2-(methacryloyloxy)-N-benzyl-N,N-dimethylethane ammonium chloride (DML; dimethylaminoethylbenzyl methacrylate chloride), N,N-diethyl-N-methyl-2-(methacryloyloxy)ethyl ammonium p-toluenesulfonate, 2-(methacryloyloxy)ethyltrimethylammonium p-toluenesulfonate, and 2-(methacryloyloxy)-N-benzyl-N,N-dimethylethane ammonium p-toluenesulfonate. In particular, structural units corresponding to N,N-diethyl-N-methyl-2-(methacryloyloxy)ethyl ammonium p-toluenesulfonate are preferred.

[0103] In the above copolymer, the copolymerization ratio of the aromatic vinyl monomer and the (meth)acrylate monomer is not particularly limited. From the viewpoint of solubility in polymerizable monomers and dispersibility in binder resins, the mass ratio of the (meth)acrylate monomer unit to the aromatic vinyl monomer unit ((meth)acrylate monomer unit / aromatic vinyl monomer unit) is preferably 0.05 to 0.35, more preferably 0.10 to 0.30, and further preferably 0.15 to 0.25.

[0104] In the present invention, the content of the copolymer A containing the functional group-containing monomer unit in a ratio of 1.50 mass % or more and 6.00 mass % or less is not particularly limited, and relative to 100 mass parts of the binding resin, as a lower limit, preferably 0.50 mass parts or more, more preferably 0.80 mass parts or more, and further preferably 1.00 mass parts or more, as an upper limit, preferably 3.00 mass parts or less, more preferably 2.50 mass parts or less, and further preferably 2.00 mass parts or less. If the content of the above-mentioned copolymer A is above the above-mentioned lower limit, the effect of suppressing the seepage of the release agent is improved, and in addition, the charge amount of the toner is easy to become appropriate, and in particular, the generation of fog caused by the low charge amount of the toner can be suppressed. If the content of the above-mentioned copolymer A is below the above-mentioned upper limit, the charge amount of the toner is easy to become appropriate, and in particular, the reduction in printing concentration caused by the high charge amount of the toner can be suppressed.

[0105] In the present invention, the content of the copolymer B containing the functional group-containing monomer unit in a ratio of 0.10% by mass or more and less than 1.50% by mass is not particularly limited, relative to 100 parts by mass of the binding resin, as a lower limit, preferably 0.50 parts by mass or more, more preferably 0.60 parts by mass or more, further preferably 0.80 parts by mass or more, as an upper limit, preferably 5.00 parts by mass or less, more preferably 3.00 parts by mass or less, further preferably 2.00 parts by mass or less. If the content of the above-mentioned copolymer B is above the above-mentioned lower limit, the effect of suppressing the oozing of the release agent is improved. If the content of the above-mentioned copolymer B is below the above-mentioned upper limit, the charge amount of the toner is easy to become appropriate, and in particular, the printing concentration reduction caused by the excessive charge amount of the toner can be suppressed.

[0106] The ratio of the content of the above-mentioned copolymer A to the content of the above-mentioned copolymer B (content of copolymer A / content of copolymer B) is not particularly limited, but is preferably 0.3 or more, more preferably 0.5 or more, and further preferably 1.0 or more as a lower limit, and is preferably 3.0 or less, more preferably 2.5 or less, and further preferably 2.0 or less as an upper limit.

[0107] If the above ratio (content of copolymer A / content of copolymer B) is above the above lower limit and below the above upper limit, the effect of suppressing the seepage of the release agent becomes higher, and the charge amount of the toner tends to become appropriate. In particular, if it is above the above lower limit, the generation of fogging caused by too low charge amount of the toner can be suppressed, and if it is below the above upper limit, the reduction in printing density caused by too high charge amount of the toner can be suppressed.

[0108] In the present invention, as the positively charged charge control resin, it is sufficient to contain at least one of the above-mentioned copolymer A and at least one of the above-mentioned copolymer B. From the viewpoint of easily obtaining the effect of the present invention, it is preferred that the above-mentioned copolymer A and the above-mentioned copolymer B are each composed of copolymers having the same composition of monomer units. In addition, copolymers having the same composition of monomer units refer to copolymers having the same type and copolymerization ratio of monomers used to synthesize the copolymers.

[0109] In the present invention, in each copolymer contained as a positively charged charge control resin, when the ratio (mass %) of the functional group-containing monomer unit is F and the content (mass parts) of the copolymer relative to 100 parts by mass of the binder resin is m, the sum of the products of F and m (F×m) calculated for each copolymer is preferably 1.80 or more and 6.00 or less, and more preferably 2.00 or more and 6.00 or less. That is, for example, in the case where each of the above-mentioned copolymer A and the above-mentioned copolymer B is contained as a positively charged charge control resin, when the ratio (mass %) of the functional group-containing monomer unit of copolymer A is F, the total product of F and m is preferably 1.80 or more and 6.00 or less, and more preferably 2.00 or more and 6.00 or less. A , the content (mass parts) of copolymer A relative to 100 parts by mass of the binder resin is m A The ratio (mass %) of the functional group-containing monomer units in copolymer B is F B , the content (mass parts) of copolymer B relative to 100 parts by mass of the binder resin is m B When the F calculated for copolymer A is A and m A The product of (F A ×m A ) and the F calculated for copolymer B B and m B The product of (F B ×m B ) and (F A ×m A +F B ×m B ) is preferably 1.80 or more and 6.00 or less, more preferably 2.00 or more and 6.00 or less. If the sum of the above products is above the above lower limit, the charge amount of the toner is sufficiently high, so the generation of fog can be suppressed. If the sum of the above products is below the above upper limit, the charge amount of the toner will not be too high, so the reduction in printing concentration can be suppressed. In addition, if the sum of the above products is below the above upper limit, the amount of the charge control resin present on the surface of the colored resin particles will not be too much, and a sufficient amount of polar resin tends to be present on the surface of the colored resin particles, so the heat resistance of the toner and the inhibitory effect of the seepage of the release agent are improved, and the generation of fog can be suppressed when the toner is stored for a long time in a high temperature and high humidity environment.

[0110] The total of the products of F and m (F×m) calculated for each of the above copolymers is more preferably 2.50 or more, more preferably 3.00 or more as the lower limit, and is more preferably 5.50 or less, more preferably 5.00 or less as the upper limit.

[0111] The proportion of the functional group-containing monomer units in copolymer A is F A (mass %) and the ratio F of the functional group-containing monomer unit of copolymer B B (mass %) difference (F A -F B ) is not particularly limited, but from the viewpoint of easily obtaining the effects of the present invention, the lower limit is preferably 0.30 or more, more preferably 0.50 or more, and further preferably 0.70 or more, and the upper limit is preferably 5.90 or less, more preferably 5.00 or less, and further preferably 1.50 or less.

[0112] In addition, when a plurality of copolymers A are included, the difference (F A -F B ) A , the value of the functional group amount in the copolymer A having the largest amount of functional groups is used. In the case of containing multiple copolymers B, as the value for calculating the above difference (F A -F B ) B , the value of the amount of functional groups in copolymer B having the least amount of functional groups is used.

[0113] The weight average molecular weight (Mw) of the copolymers A and B is not particularly limited, but is preferably 8000 to 28000, more preferably 10000 to 25000, and further preferably 15000 to 23000. If the weight average molecular weight (Mw) is above the lower limit, the storage stability and printing durability can be suppressed from decreasing, and if it is below the upper limit, the fixability can be suppressed from decreasing. In addition, if the weight average molecular weight (Mw) is within the above range, the charge control resin can be appropriately dispersed in the polymerizable monomer composition, so it is easy to obtain a toner that is given a stable charge over time.

[0114] In the present invention, the weight average molecular weight Mw is a polystyrene-equivalent value measured by gel permeation chromatography (GPC) using tetrahydrofuran.

[0115] In addition, within the range not impairing the effect of the present invention, the polymerizable monomer composition may further contain a charge control agent different from the above-mentioned copolymers A and B. In this case, from the viewpoint of easily obtaining the effect of the present invention, the content of the above-mentioned copolymers A and B is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, and even more preferably 99 parts by mass or more in 100 parts by mass of the total amount of the charge control agent.

[0116] (Polar resin)

[0117] As the polar resin, a resin having an acid value of 0.5 mgKOH / g to 8.0 mgKOH / g can be used, and preferably a resin having an acid value of 0.5 mgKOH / g to 5.0 mgKOH / g can be used.

[0118] As the polar resin, from the viewpoint of suppressing printing defects in a high temperature and high humidity environment, an acrylate copolymer having an acidic group is preferably used. As the acrylate copolymer having an acidic group, for example, a copolymer of (meth)acrylate and (meth)acrylic acid is preferably used.

[0119] In the present invention, (meth)acrylic acid refers to acrylic acid and methacrylic acid, respectively. A copolymer of (meth)acrylic acid ester and (meth)acrylic acid refers to a copolymer of at least one selected from acrylic acid ester and methacrylic acid ester and at least one selected from acrylic acid and methacrylic acid.

[0120] Examples of the copolymer include copolymers of acrylate and acrylic acid; copolymers of acrylate and methacrylic acid; copolymers of methacrylate and acrylic acid; copolymers of methacrylate and methacrylic acid; copolymers of acrylate, methacrylate and acrylic acid; copolymers of acrylate, methacrylate and methacrylic acid; and copolymers of acrylate, methacrylate, acrylic acid and methacrylic acid. Among these, copolymers of acrylate, methacrylate and acrylic acid are preferred.

[0121] Examples of the (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, sec-pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, neohexyl (meth)acrylate, sec-hexyl (meth)acrylate, and tert-hexyl (meth)acrylate.

[0122] As the acrylic acid ester, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, and n-butyl acrylate are particularly preferred, and ethyl acrylate and n-butyl acrylate are more preferred.

[0123] As the methacrylate, methyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, and n-butyl methacrylate are particularly preferred, and methyl methacrylate is more preferred.

[0124] The mass ratio of each monomer unit in the acrylic ester copolymer is preferably adjusted so as to satisfy the acid value, weight average molecular weight Mw, and glass transition temperature described below.

[0125] The content of the (meth)acrylic acid unit in 100% by mass of all monomer units constituting the acrylic ester copolymer is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and still more preferably 0.3% by mass or more as the lower limit, and is preferably 1.0% by mass or less, more preferably 0.6% by mass or less, and still more preferably 0.5% by mass or less as the upper limit.

[0126] The content of the (meth)acrylate units in 100% by mass of all monomer units constituting the acrylic ester copolymer is preferably 99.0% by mass or more, more preferably 99.4% by mass or more, and even more preferably 99.5% by mass or more as the lower limit, and is preferably 99.95% by mass or less, more preferably 99.9% by mass or less, and even more preferably 99.7% by mass or less as the upper limit.

[0127] In the range that does not impair the effect of the present invention, the above-mentioned acrylate copolymer may contain other monomer units different from the (meth)acrylate unit and the (meth)acrylic acid unit. As such other monomers, for example, styrene derivatives, nitrile compounds and amide compounds exemplified in the monovinyl monomer constituting the above-mentioned binder resin can be cited.

[0128] In the acrylic ester copolymer, the content of the other monomer units is preferably 10 parts by mass or less, more preferably 2 parts by mass or less, and most preferably 0 parts by mass, based on 100 parts by mass of the (meth)acrylic ester units.

[0129] The acid value of the polar resin can be as long as it is 0.5 mgKOH / g or more and 8.0 mgKOH / g or less, preferably 0.5 mgKOH / g or more and 5.0 mgKOH / g or less. As a lower limit, it is more preferably 1.0 mgKOH / g or more, and more preferably 2.0 mgKOH / g or more. As an upper limit, it is more preferably 4.0 mgKOH / g or less, and more preferably 3.0 mgKOH / g or less. If the acid value of the polar resin is above the lower limit, the charge of the toner can be appropriately reduced, so that the reduction in printing concentration can be suppressed. If the acid value of the polar resin is below the upper limit, the change in the charge of the toner with changes in temperature and humidity can be suppressed.

[0130] In the present invention, the acid value of the resin is measured in accordance with JIS K 0070.

[0131] The weight average molecular weight (Mw) of the polar resin is not particularly limited, but is preferably 6,000 or more, more preferably 7,000 or more, and further preferably 9,000 or more as a lower limit, and is preferably 50,000 or less, more preferably 45,000 or less, and further preferably 40,000 or less as an upper limit.

[0132] If the weight average molecular weight (Mw) of the polar resin is above the lower limit, the effect of suppressing the bleeding of the release agent is improved. If it is below the upper limit, the heat resistance of the toner can be suppressed from decreasing, and the generation of fogging when the toner is stored for a long time in a high temperature and high humidity environment can be suppressed.

[0133] The glass transition temperature Tg of the polar resin is not particularly limited, but is preferably 60°C or higher, more preferably 65°C or higher, and further preferably 70°C or higher as the lower limit, and is preferably 85°C or lower, more preferably 80°C or lower, and further preferably 77°C or lower as the upper limit.

[0134] When the glass transition temperature Tg of the polar resin is within the above range, it is possible to suppress a decrease in heat resistance of the toner and suppress the occurrence of fogging when the toner is used and stored for a long period of time under a high-temperature and high-humidity environment.

[0135] In the present invention, the glass transition temperature Tg can be determined in accordance with ASTM D3418-82.

[0136] Regarding the content of the above-mentioned polar resin relative to 100 parts by mass of the binder resin, as a lower limit, it is preferably 0.30 parts by mass or more, more preferably 0.40 parts by mass or more, and further preferably 0.50 parts by mass or more, and as an upper limit, it is preferably 3.00 parts by mass or less, more preferably 2.00 parts by mass or less, and further preferably 1.50 parts by mass or less.

[0137] If the content of the polar resin is above the lower limit, the effect of suppressing the seepage of the release agent is improved. If the content of the polar resin is below the upper limit, the charge amount of the toner is likely to become appropriate, and in particular, the generation of fogging caused by too low a charge amount of the toner can be suppressed, and in addition, the change of the charge amount of the toner accompanying the change of temperature and humidity can be suppressed.

[0138] The polar resin may be a commercially available product, and may be produced by a known polymerization method such as solution polymerization, aqueous solution polymerization, ion polymerization, high temperature and high pressure polymerization, or suspension polymerization.

[0139] Typical examples of the method for producing the polar resin are as follows. In addition, the method for producing the polar resin is not limited to the following typical examples.

[0140] First, a solvent is appropriately added to a reaction vessel, the reaction vessel is replaced with an inactive environment, and then the temperature is raised, and the raw monomer is added to the reaction vessel. At this time, a polymerization initiator is preferably added simultaneously. In addition, a mixture of the raw monomer and the polymerization initiator is preferably slowly added dropwise to the reaction vessel. Next, the temperature is raised to a temperature at which the polymerization reaction proceeds, and polymerization is initiated. After the polymerization is terminated, the solvent is appropriately distilled off to obtain the desired polar resin.

[0141] When the acid value (mgKOH / g) of the polar resin is x and the content (parts by mass) of the polar resin relative to 100 parts by mass of the binder resin is m P The ratio (mass %) of the functional group-containing monomer units in the copolymer A is F A , the content (mass parts) of the copolymer A relative to 100 parts by mass of the binder resin is m A When X and m p The product of (X×m P ) and F A and m A The product of (F A ×m A ) is the absolute value of the difference (|X×m P -F A ×m A |) is preferably 2.50 or less. This can suppress the change in the charge amount of the toner accompanying changes in temperature and humidity. The absolute value of the above difference (|X×m P -F A ×m A |) is more preferably 2.00 or less, and further preferably 1.00 or less. In addition, the lower limit is not particularly limited, and may be 0, or may be, for example, 0.20 or more.

[0142] In addition, when multiple polar resins are included, the "X×mP ” is the “X×m P In the case of containing multiple copolymers A, the "F A ×m A " is the "F A ×m A The sum of .

[0143] (Styrene-based thermoplastic elastomer)

[0144] The polymerizable monomer composition preferably contains a styrene-based thermoplastic elastomer. This improves the dispersibility of the release agent and thus makes it less likely for the release agent to bleed out.

[0145] In the present invention, the styrene-based thermoplastic elastomer refers to a random, block, graft or other copolymer of a styrene-based monomer, that is, an aromatic vinyl monomer and another monomer copolymerizable with the aromatic vinyl monomer, and a hydrogenated product of such a copolymer.

[0146] Thermoplastic elastomers typically refer to materials that can be deformed to 200% by volume by a small external force at room temperature (20° C.) with the original volume being 100% by volume, and recover to less than 130% by volume when the external force is removed.

[0147] As the styrene-based thermoplastic elastomer, for example, a conjugated diene-aromatic vinyl-based thermoplastic elastomer can be preferably used. Unhydrogenated conjugated diene-aromatic vinyl-based thermoplastic elastomers are particularly preferred. Here, the conjugated diene-aromatic vinyl-based thermoplastic elastomer refers to a polymer having a structural unit derived from a conjugated diene monomer and a structural unit derived from an aromatic vinyl monomer.

[0148] As the above-mentioned conjugated diene-aromatic vinyl-based thermoplastic elastomer, for example, random, block, graft, etc. copolymers of conjugated diene monomers and aromatic vinyl monomers and other monomers copolymerizable with these monomers used as needed, and hydrogenated products of such copolymers, etc. From the viewpoint of improving the fixability of the toner, block copolymers containing at least one aromatic vinyl polymer block and at least one conjugated diene polymer block are particularly preferred.

[0149] Hereinafter, a block copolymer (hereinafter sometimes referred to as "block copolymer") comprising at least one aromatic vinyl polymer block and at least one conjugated diene polymer block as a representative example of a styrene-based thermoplastic elastomer is described. The block copolymer comprises at least one aromatic vinyl polymer block obtained by polymerizing an aromatic vinyl monomer and at least one conjugated diene polymer block obtained by polymerizing a conjugated diene monomer.

[0150] As the aromatic vinyl monomer used in the aromatic vinyl polymer block, for example, the same monomer as the aromatic vinyl monomer that can be used in the above-mentioned charge control resin can be cited, and styrene is particularly preferred. In each aromatic vinyl polymer block possessed by the above-mentioned block copolymer, the aromatic vinyl monomer can be used alone or in combination of two or more. In addition, when the block copolymer has a plurality of aromatic vinyl polymer blocks, each aromatic vinyl polymer block can be composed of the same aromatic vinyl monomer unit or different aromatic vinyl monomer units.

[0151] As long as the aromatic vinyl polymer block is the main repeating unit, it may also contain monomer units other than the aromatic vinyl monomer unit. As other monomers that can be used in the aromatic vinyl polymer block, there can be cited: conjugated diene monomers such as 1,3-butadiene and isoprene (2-methyl-1,3-butadiene); α,β-unsaturated nitrile monomers, unsaturated carboxylic acid or anhydride monomers, unsaturated carboxylic acid ester monomers, non-conjugated diene monomers, etc. The content of monomer units other than the aromatic vinyl monomer unit in the aromatic vinyl polymer block is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 0% by mass.

[0152] As the conjugated diene monomer used in the conjugated diene polymer block, for example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc. can be cited. Among these, from the viewpoint of good effect of improving storage stability and low-temperature fixability, it is preferred to use at least one selected from 1,3-butadiene and isoprene, and isoprene is particularly preferred. In each conjugated diene polymer block possessed by the above-mentioned block copolymer, these conjugated diene monomers can be used alone or in combination of two or more. In addition, in the case where the block copolymer has a plurality of conjugated diene polymer blocks, each conjugated diene polymer block can be composed of the same conjugated diene monomer unit, or it can be composed of different conjugated diene monomer units. Furthermore, a part of the unsaturated bonds of each conjugated diene polymer block can also be hydrogenated.

[0153] As long as the conjugated diene monomer unit is the main repeating unit, the conjugated diene polymer block may also contain monomer units other than this. As other monomers that can be used in the conjugated diene polymer block, aromatic vinyl monomers such as styrene and α-methylstyrene, α, β-unsaturated nitrile monomers, unsaturated carboxylic acid monomers, unsaturated carboxylic anhydride monomers, unsaturated carboxylic ester monomers, non-conjugated diene monomers, etc. can be cited. The content of monomer units other than the conjugated diene monomer unit in the conjugated diene polymer block is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 0% by mass.

[0154] The vinyl bond content of the conjugated diene polymer block (the ratio of 1,2-vinyl bond units and 3,4-vinyl bond units in all conjugated diene monomer units in the conjugated diene polymer block) is not particularly limited, but is preferably 1 to 20 mol %, more preferably 2 to 15 mol %, and particularly preferably 3 to 10 mol %.

[0155] As long as the block copolymers respectively contain at least one aromatic vinyl polymer block and a conjugated diene polymer block, the number of polymer blocks and their bonding modes are not particularly limited. As specific examples of the block copolymers, the following block copolymers can be cited. In the following specific examples, Ar represents an aromatic vinyl polymer block, D represents a conjugated diene polymer block, X represents a residue of a coupling agent, and n represents an integer greater than 2.

[0156] (a) Aromatic vinyl-conjugated diene block copolymer represented by the form of Ar-D

[0157] (b) Ar-D-Ar or (Ar-D) n Aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by the form of -X

[0158] (c) D-Ar-D or (D-Ar) n Conjugated diene-aromatic vinyl-conjugated diene block copolymer represented by the form of -X

[0159] (d) Aromatic vinyl-conjugated diene-aromatic vinyl-conjugated diene block copolymer represented by the form of Ar-D-Ar-D

[0160] (e) A block copolymer composition in which two or more of the above (a) to (d) are arbitrarily combined.

[0161] The toner of the present invention preferably contains at least the above-mentioned (b), and more preferably contains at least the above-mentioned (a) and (b), as the styrene-based thermoplastic elastomer, from the viewpoint of improving the fixing property.

[0162] When the above-mentioned (b) is contained as a styrene-based thermoplastic elastomer, the content of the above-mentioned (b) relative to 100% by mass of the styrene-based thermoplastic elastomer is preferably 2% by mass or more, more preferably 5% by mass or more as a lower limit, and is preferably 60% by mass or less, more preferably 50% by mass or less as an upper limit.

[0163] When the above-mentioned (a) is contained as a styrene-based thermoplastic elastomer, the content of the above-mentioned (a) relative to 100% by mass of the styrene-based thermoplastic elastomer is preferably 40% by mass or more, preferably 50% by mass or more, and more preferably 55% by mass or more as a lower limit, and is not particularly limited as an upper limit, but is preferably 98% by mass or less, and more preferably 95% by mass or less.

[0164] When (a) and (b) are contained as the styrene-based thermoplastic elastomer, the content of (b) is preferably 2 to 60 parts by mass, more preferably 5 to 50 parts by mass, based on 100 parts by mass of the total mass of (a) and (b).

[0165] When the contents of (a) and (b) are within the above ranges, the fixing property of the toner is improved, thereby suppressing a decrease in print density, and the charge amount of the toner tends to be appropriate, and bleeding of the release agent tends to be suppressed.

[0166] In the above (a), the weight average molecular weight (Mw(Ar)) of the aromatic vinyl polymer block Ar is not particularly limited, but is preferably 10,000 to 50,000, and more preferably 15,000 to 30,000.

[0167] In the above (a), the weight average molecular weight (Mw(D)) of the conjugated diene polymer block D is not particularly limited, but is preferably 50,000 to 200,000, and more preferably 60,000 to 150,000.

[0168] In the above (b), the weight average molecular weight (Mw(Ar)) of the aromatic vinyl polymer block Ar is not particularly limited, but is preferably 20,000 to 70,000, and more preferably 25,000 to 50,000.

[0169] In the above (b), the weight average molecular weight (Mw(D)) of the conjugated diene polymer block D is not particularly limited, but is preferably 100,000 to 300,000, and more preferably 120,000 to 250,000.

[0170] The content ratio of the aromatic vinyl monomer units in the block copolymer relative to the total monomer units is preferably 10 to 30% by mass, more preferably 12 to 25% by mass, and further preferably 15 to 25% by mass. By making the content ratio of the aromatic vinyl monomer units within the above range, the affinity of the block copolymer for the release agent and the affinity of the block copolymer for the binder resin can be highly balanced, and the storage stability and low-temperature fixing property of the obtained toner can be made more excellent.

[0171] The content of the aromatic vinyl monomer unit in the block copolymer is determined by ozonolysis of the block copolymer according to the method described in Rubber Chem. Technol., 45, 1295 (1972), followed by reduction with lithium aluminum hydride, as long as all the polymer components constituting the block copolymer consist only of aromatic vinyl monomer units and conjugated diene monomer units. In this way, the conjugated diene monomer unit portion is decomposed and only the aromatic vinyl monomer unit portion is extracted, so that the total aromatic vinyl monomer unit content can be easily measured.

[0172] The weight average molecular weight (Mw) of the aromatic vinyl polymer block in the block copolymer is not particularly limited, but is preferably 10,000 to 50,000, and more preferably 20,000 to 40,000.

[0173] The weight average molecular weight (Mw) of the conjugated diene polymer block in the block copolymer is not particularly limited, but is preferably 50,000 to 200,000, and more preferably 60,000 to 180,000.

[0174] The melt index (MI) of the block copolymer is not particularly limited, and can be selected from the range of, for example, 1 to 1000 g / 10 min, preferably 5 to 30 g / 10 min, as a value measured in accordance with ASTM D-1238 (G condition, 200° C., 5 kg).

[0175] The block copolymer can be produced by a conventional method. For example, the following method can be used to produce the block copolymer: an aromatic vinyl monomer and a conjugated diene monomer are polymerized in sequence by an anionic living polymerization method to form a polymer block, and a coupling agent is reacted as needed to perform coupling.

[0176] A mixture containing at least the above-mentioned (a) and (b) which is preferably used as the above-mentioned block copolymer can be produced by, for example, the following method.

[0177] First, an aromatic vinyl monomer is polymerized by an anionic living polymerization method, and then a conjugated diene monomer is added and polymerized, thereby obtaining a diblock copolymer having an active terminal. Next, the following method can be cited: less than 1 molar equivalent of a coupling agent is added to the active terminal of the diblock copolymer having an active terminal, thereby causing a portion of the diblock copolymer having an active terminal to undergo a coupling reaction, thereby obtaining (Ar-D) n The aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-X is prepared by adding a polymerization terminator to deactivate the remaining diblock copolymer having an active terminal, thereby obtaining a diblock copolymer represented by Ar-D. In addition, at this time, as a coupling agent, a bifunctional coupling agent such as dichlorosilane, monomethyldichlorosilane, dimethyldichlorosilane, diphenyldimethoxysilane, diphenyldiethoxysilane, dichloroethane, dibromoethane, dichloromethane, dibromomethane, etc. is used, thereby obtaining an aromatic vinyl-conjugated diene-aromatic vinyl block copolymer represented by Ar-D-Ar (D contains the residue of the coupling agent).

[0178] In addition, as the styrene-based thermoplastic elastomer, a random copolymer of an aromatic vinyl monomer and a conjugated diene monomer can be used instead of the block copolymer. The random copolymer of an aromatic vinyl monomer and a conjugated diene monomer can be produced by, for example, living anionic polymerization using an organic alkali metal compound as a polymerization initiator.

[0179] Examples of the organic alkali metal compound include organic lithium compounds, organic sodium compounds, and organic potassium compounds. Specifically, organic monolithium compounds such as n-butyl lithium, sec-butyl lithium, tert-butyl lithium, hexyl lithium, phenyl lithium, and stilbene lithium; organic polylithium compounds such as dilithium methane, 1,4-dilithium butane, 1,4-dilithium-2-ethylcyclohexane, 1,3,5-trilithium benzene, and 1,3,5-tri(lithium methyl) benzene; organic sodium compounds such as sodium naphthalene; organic potassium compounds such as potassium naphthalene, etc. Among these organic metal compounds, n-butyl lithium is preferably used.

[0180] The content ratio of the aromatic vinyl monomer unit in the random copolymer of the aromatic vinyl monomer and the conjugated diene monomer relative to the total monomer units is not particularly limited, and is preferably 50% by mass or less, more preferably 45% by mass or less, and further preferably 40% by mass or less. By making the content ratio of the aromatic vinyl monomer unit below the above upper limit, the affinity of the random copolymer for the release agent and the affinity of the block copolymer for the binder resin can be highly balanced, and the storage stability and low-temperature fixability of the obtained toner can be made more excellent.

[0181] The weight average molecular weight (Mw) of the styrene-based thermoplastic elastomer is not particularly limited, but is preferably 60000 to 350000, more preferably 80000 to 250000. When the weight average molecular weight (Mw) of the styrene-based thermoplastic elastomer is within the above range, the storage stability and low-temperature fixing property of the toner can be improved, and the occurrence of printing defects can be suppressed.

[0182] The content of the styrene-based thermoplastic elastomer is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and further preferably 3 parts by mass or more, relative to 100 parts by mass of the binder resin, as a lower limit, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, as an upper limit.

[0183] If the content of the styrene-based thermoplastic elastomer is greater than the lower limit, the effect of suppressing the bleeding of the release agent is improved. If the content of the styrene-based thermoplastic elastomer is less than the upper limit, the toner is easily diffused during fixing, thereby suppressing the reduction in printing density.

[0184] (Release agent)

[0185] As a release agent, any release agent commonly used as a release agent or softener for colorants can be used without particular limitation. From the viewpoint of easily and effectively exerting the effect of suppressing bleeding through the combination of the above-mentioned positively charged charge control resin and the polar resin, a fatty acid ester compound having a number average molecular weight (Mn) of greater than 500 and less than 2000 is preferred.

[0186] Here, the "fatty acid ester compound" refers to a product obtained by an esterification reaction of at least one alcohol selected from monohydric alcohols and polyhydric alcohols and at least one fatty acid selected from saturated fatty acids and unsaturated fatty acids.

[0187] Examples of the monohydric alcohol include: saturated monohydric aliphatic alcohols such as methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 1-hexanol, octanol, 2-ethyl-1-hexanol, nonanol, lauryl alcohol, hexadecanol, stearyl alcohol, and behenyl alcohol; unsaturated monohydric aliphatic alcohols such as allyl alcohol, methallyl alcohol, crotyl alcohol, and oleyl alcohol; alicyclic monohydric alcohols such as cyclohexanol; and aromatic monohydric alcohols such as phenol, benzyl alcohol (benzyl alcohol), methylphenol (cresol), p-ethylphenol, xylenol (xylenol), nonylphenol, dodecylphenol, phenylphenol, and naphthol.

[0188] Examples of the polyhydric alcohol include divalent saturated aliphatic alcohols such as ethylene glycol and propylene glycol; divalent aromatic alcohols such as catechol and hydroquinone; and trivalent or higher valent saturated aliphatic alcohols such as glycerol, pentaerythritol, dipentaerythritol and polyglycerol.

[0189] Among these monohydric alcohols and polyhydric alcohols, mono- to tetrahydric saturated aliphatic alcohols are preferred, and behenyl alcohol and pentaerythritol are particularly preferred.

[0190] The carbon number of the fatty acid as the raw material of the fatty acid ester compound is preferably 12 or more, more preferably 14 or more, and further preferably 16 or more as the lower limit, and is preferably 24 or less, more preferably 22 or less, and further preferably 18 or less as the upper limit. If the carbon number of the fatty acid is above the lower limit, it is easy to suppress the exudation of the fatty acid ester compound. If the carbon number of the fatty acid is below the upper limit, it is possible to suppress the reduction of the heat resistance of the toner, and suppress the generation of fog when the toner is used and stored for a long time under a high temperature and high humidity environment.

[0191] Furthermore, from the viewpoint of easily obtaining a fatty acid ester compound having a number average molecular weight (Mn) of 500 or more and less than 2,000, a saturated fatty acid having a carbon number within the above range is particularly preferred.

[0192] The saturated fatty acid is not particularly limited, and examples thereof include lauric acid (carbon number 12), myristic acid (carbon number 14), pentadecanoic acid (carbon number 15), palmitic acid (carbon number 16), heptadecanoic acid (carbon number 17), stearic acid (carbon number 18), arachidic acid (carbon number 20), and behenic acid (carbon number 22). Behenic acid (carbon number 22), stearic acid (carbon number 18), and arachidic acid (carbon number 20) are particularly preferred.

[0193] The unsaturated fatty acid is not particularly limited, and examples thereof include the following.

[0194] Palmitoleic acid (CH3(CH2)5CH=CH(CH2)7COOH)

[0195] Oleic acid (CH3(CH2)7CH=CH(CH2)7COOH)

[0196] Vaccinium oleate (CH3(CH2)5CH=CH(CH2)9COOH)

[0197] Linoleic acid (CH3(CH2)3(CH2CH=CH)2(CH2)7COOH)

[0198] (9,12,15)-linolenic acid (CH3(CH2CH=CH)3(CH2)7COOH)

[0199] ·(6,9,12)-linolenic acid(CH3(CH2)3(CH2CH=CH)3(CH2)4COOH)

[0200] Eleurotic acid (CH3(CH2)3(CH=CH)3(CH2)7COOH)

[0201] Arachidonic acid (CH3(CH2)3(CH2CH=CH)4(CH2)3COOH)

[0202] In addition, the above-mentioned fatty acids can be used alone or in combination of two or more.

[0203] From the viewpoint of improving the low-temperature fixing property of the toner due to the sharp melting property of the fatty acid ester compound, the esterification rate of the fatty acid ester compound is preferably 92% or more, more preferably 95% or more, and even more preferably 97% or more.

[0204] The esterification rate of fatty acid ester compounds refers to the ratio of the number of hydroxyl groups bonded to fatty acid esters to the total number of hydroxyl groups possessed by the raw alcohol of the fatty acid ester compounds. The esterification rate of fatty acid ester compounds can be calculated by measuring the saponification value (SV), hydroxyl value (OHV), and acid value (AV) of the fatty acid ester compounds respectively and using the following formula.

[0205]

[0206] The saponification value (SV) and acid value (AV) of the fatty acid ester compound are measured in accordance with JIS K 0070, and the hydroxyl value (OHV) of the fatty acid ester compound is measured in accordance with JIS K 1557.

[0207] The fatty acid ester compound may be any of a monoester, a diester, a triester, a tetraester or a polyester, and monoesters are preferred from the viewpoint of improving the storage property of the toner and suppressing the aggregation of the toner under a high temperature and high humidity environment. The agglomerates of the toner are placed on the developing roller in an uncharged state, which causes fogging, and thus the generation of fog can be suppressed by suppressing the aggregation of the toner. In addition, monoesters are generally easy to ooze out, but in the toner of the present invention, the oozing out of the release agent can be suppressed, so if a monoester is used as a release agent, the effect of the present invention can be particularly effectively exerted.

[0208] Examples of the monoester include behenyl palmitate, behenyl stearate, behenyl arachidate, behenyl behenate, arachidate palmitate, arachidate stearate, arachidate arachidate, arachidate behenate, stearyl stearate, stearyl arachidate, stearyl behenate, cetyl arachidate, cetyl behenate, etc. From the viewpoint of improving the low-temperature fixability of the toner, facilitating the toner to melt and spread during fixing, improving the coverage on the paper surface, and thereby improving the print density, behenyl stearate, behenyl palmitate, and stearyl behenate are particularly preferred, and behenyl stearate is particularly preferred.

[0209] Regarding the number average molecular weight (Mn) of the above-mentioned fatty acid ester compound, from the perspective of improving the low-temperature fixing ability of the colorant and inhibiting the bleeding of the fatty acid ester compound, the lower limit is preferably 500 or more, and more preferably 550 or more. From the perspective of the easy diffusion of the colorant during fixing and the suppression of the reduction in printing concentration, the upper limit is preferably less than 2000, more preferably 1500 or less, further preferably 1000 or less, and further preferably 700 or less.

[0210] In addition, fatty acid ester compounds having a number average molecular weight (Mn) within the above range are prone to seepage, but in the colorant of the present invention, since the seepage of the release agent can be suppressed, if a fatty acid ester compound having a number average molecular weight (Mn) within the above range is used as a release agent, the effect of the present invention can be particularly effectively exerted.

[0211] The melting point of the release agent is preferably within a range of 50 to 90°C, more preferably within a range of 60 to 85°C, and still more preferably within a range of 65 to 75°C.

[0212] Commercially available products may be used as the fatty acid ester compound. Examples of commercially available products of the fatty acid ester compound include "WEP2", "WEP3", "WEP4", "WEP5", "WE6", and "WE11" (these are trade names) manufactured by NOF Corporation.

[0213] In the present invention, other release agents can be used together with the above-mentioned fatty acid ester compound. Specific examples of the above-mentioned other release agents include: low molecular weight polyolefin wax, modified wax thereof; plant-based natural waxes such as jojoba wax, petroleum waxes such as paraffin wax; mineral waxes such as ozokerite; synthetic waxes such as Fischer-Tropsch wax, etc. The above-mentioned other release agents can be used alone or in combination of two or more.

[0214] The content of the release agent is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and further preferably 15 parts by mass or more, relative to 100 parts by mass of the binder resin as the lower limit, and is preferably 30 parts by mass or less, and more preferably 25 parts by mass or less as the upper limit.

[0215] If the content of the release agent is above the lower limit, a toner having excellent low-temperature fixability can be obtained, and the toner is easily diffused during fixing, thereby suppressing a decrease in print density. If the content of the release agent is below the upper limit, bleeding of the release agent can be suppressed.

[0216] The content of the fatty acid ester compound in 100 parts by mass of the release agent is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, and even more preferably 99 parts by mass or more.

[0217] (Molecular weight regulator)

[0218] In the polymerizable monomer composition, when polymerizing the polymerizable monomer, it is preferred to use a molecular weight modifier as another additive.

[0219] The molecular weight modifier is not particularly limited as long as it is a molecular weight modifier generally used as a molecular weight modifier for toner, and examples thereof include mercaptans such as tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, and 2,2,4,6,6-pentamethylheptane-4-mercaptan; thiuram disulfides such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, N,N'-dimethyl-N,N'-diphenylthiuram disulfide, and N,N'-dioctadecyl-N,N'-diisopropylthiuram disulfide, etc. These molecular weight modifiers may be used alone or in combination of two or more.

[0220] The content of the molecular weight modifier is usually 0.01 to 10 parts by mass, preferably 0.1 to 5 parts by mass, based on 100 parts by mass of the monovinyl monomer.

[0221] (A-2) Suspension step of obtaining a suspension (droplet formation step)

[0222] Next, after dispersing the polymerizable monomer composition in an aqueous medium containing a dispersion stabilizer and adding a polymerization initiator, droplets of the polymerizable monomer composition are formed. The polymerization initiator may be added after the polymerizable monomer composition is dispersed in the aqueous medium and before droplets are formed as described above, or may be added to the polymerizable monomer composition before being dispersed in the aqueous medium.

[0223] Examples of the polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate; azo compounds such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile) and 2,2'-azobisisobutyronitrile; and organic peroxides such as di-tert-butyl peroxide, benzoyl peroxide, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylbutyrate, tert-hexyl peroxy-2-ethylbutyrate, tert-butyl peroxy-2-diethylacetate, diisopropyl peroxydicarbonate, di-tert-butyl peroxyisophthalate and tert-butyl peroxyisobutyrate. Among these, organic peroxides are preferably used from the viewpoint that residual polymerizable monomers can be reduced and the printing durability of the obtained toner is excellent. Among organic peroxides, peroxyesters are preferred from the viewpoint that the initiator efficiency is high and residual polymerizable monomers can be reduced, and non-aromatic peroxyesters, i.e., peroxyesters without an aromatic ring, are more preferred.

[0224] These polymerization initiators can be used alone or in combination of two or more.

[0225] The amount of the polymerization initiator used in the polymerization of the polymerizable monomer composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 15 parts by mass, and even more preferably 1 to 10 parts by mass, based on 100 parts by mass of the monovinyl monomer.

[0226] In the present invention, the aqueous medium refers to a medium containing water as a main component, and is typically water.

[0227] It is preferred that the aqueous medium contains a dispersion stabilizer. Examples of the dispersion stabilizer include sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; inorganic compounds such as metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and iron hydroxide; water-soluble polymers such as polyvinyl alcohol, methylcellulose, and gelatin; anionic surfactants; nonionic surfactants; organic compounds such as amphoteric surfactants. The above dispersion stabilizers can be used alone or in combination of two or more.

[0228] Among the above-mentioned dispersion stabilizers, inorganic compounds are preferred, and colloids of metal hydroxides that are sparingly soluble in water are particularly preferred. By using inorganic compounds, particularly colloids of metal hydroxides that are sparingly soluble in water, the particle size distribution of the colored resin particles can be narrowed, and the amount of the dispersion stabilizer remaining after washing can be reduced, so that the obtained toner can reproduce images clearly and has excellent environmental stability.

[0229] The colloid of the sparingly water-soluble metal hydroxide can be prepared, for example, by reacting at least one selected from an alkali metal hydroxide salt and an alkaline earth metal hydroxide salt with a water-soluble polyvalent metal salt (except the alkaline earth metal hydroxide salt) in an aqueous medium.

[0230] Examples of the alkali metal hydroxide salt include lithium hydroxide, sodium hydroxide, potassium hydroxide, etc. Examples of the alkaline earth metal hydroxide salt include barium hydroxide, calcium hydroxide, etc.

[0231] As the water-soluble polyvalent metal salt, any polyvalent metal salt showing water solubility other than the compounds belonging to the above-mentioned alkaline earth metal hydroxide salts may be mentioned, for example: magnesium metal salts such as magnesium chloride, magnesium phosphate, and magnesium sulfate; calcium metal salts such as calcium chloride, calcium nitrate, calcium acetate, and calcium sulfate; aluminum metal salts such as aluminum chloride and aluminum sulfate; barium salts such as barium chloride, barium nitrate, and barium acetate; zinc salts such as zinc chloride, zinc nitrate, and zinc acetate, etc. Among these, magnesium metal salts, calcium metal salts, and aluminum metal salts are preferred, magnesium metal salts are more preferred, and magnesium chloride is particularly preferred.

[0232] The content of the dispersion stabilizer can be appropriately adjusted in a manner to obtain a toner with a desired particle size, and is not particularly limited. It is preferably 0.5 to 10 parts by mass, and more preferably 1.0 to 8.0 parts by mass, relative to 100 parts by mass of the polymerizable monomer in the above-mentioned polymerizable monomer composition. By making the content of the dispersion stabilizer above the above-mentioned lower limit, the droplets of the polymerizable monomer composition can be fully dispersed in a manner that does not aggregate in the suspension. On the other hand, by making the content of the dispersion stabilizer below the above-mentioned upper limit, the viscosity of the suspension can be prevented from increasing during granulation, avoiding the undesirable situation that the suspension sticks to the granulator.

[0233] The content of the dispersion stabilizer is usually 1 to 15 parts by mass, preferably 1 to 8 parts by mass, relative to 100 parts by mass of the aqueous medium.

[0234] By placing the polymerizable monomer composition into an aqueous medium containing a dispersion stabilizer and vigorously stirring the mixture, a suspension in which droplets of the polymerizable monomer composition are dispersed in the aqueous medium can be obtained.

[0235] The strong stirring for forming droplets of the polymerizable monomer composition is not particularly limited and can be carried out using a disperser such as Milder (trade name) manufactured by Ohyo Kiko Co., Ltd., Cavitron (trade name) manufactured by Eurotec Co., Ltd., a horizontal or vertical pipeline disperser such as a pipeline disperser manufactured by Aika (for example, DISPAX-REACTOR (registered trademark) DRS (trade name)); an emulsifying disperser such as the HOMOMIXER MARK II series manufactured by Plemix Corporation.

[0236] The time of stirring performed in the suspension step can be appropriately adjusted according to the amount of the polymerizable monomer composition, and is not particularly limited.

[0237] (A-3) Polymerization step

[0238] After forming droplets of the polymerizable monomer composition as described above in (A-2), the polymerizable monomer composition is subjected to a polymerization reaction in the presence of a polymerization initiator to form colored resin particles. That is, a suspension in which droplets of the polymerizable monomer composition are dispersed is heated to allow the polymerization reaction of the polymerizable monomer to proceed, thereby obtaining an aqueous dispersion of colored resin particles.

[0239] The heating temperature when the suspension is subjected to the polymerization reaction is not particularly limited. From the viewpoint of rapidly advancing the polymerization reaction, it is preferably 50° C. or higher, more preferably 60° C. or higher. On the other hand, from the viewpoint of suppressing rapid progress of the polymerization reaction and stabilizing the quality of the obtained toner, it is preferably 95° C. or lower.

[0240] The polymerization reaction time is preferably 1 to 20 hours, more preferably 2 to 15 hours.

[0241] In order to carry out polymerization in a state where droplets of the polymerizable monomer composition are stably dispersed, in this polymerization step, the polymerization reaction may be carried out while performing a dispersion treatment by stirring, following the suspension step (droplet forming step) of obtaining a suspension in (A-2).

[0242] In the present invention, the colored resin particles obtained by the above-mentioned polymerization step can be added with an external additive and used as a toner. It is preferable to use the colored resin particles obtained by the above-mentioned polymerization step as the core layer of the so-called core-shell type (or also called "capsule type") colored resin particles. The core-shell type colored resin particles have a structure in which the outer side of the core layer is coated with a shell layer formed of a material different from the core layer. By coating the core layer composed of a material having a low softening point with a material having a higher softening point than the core layer, the low-temperature fixability and storage property of the toner can be improved in a well-balanced manner.

[0243] In addition, regarding the core-shell type colored resin particles, since the shell inhibits the embedding of external additives, the deterioration of the colorant caused by the embedding of external additives can be inhibited. As a result, the charge of the colorant is easily maintained during continuous printing, and the occurrence of printing defects can be inhibited. From this perspective, core-shell type colored resin particles are preferred.

[0244] The method for producing the core-shell type colored resin particles using the colored resin particles obtained in the above polymerization step is not particularly limited, and the colored resin particles can be produced by a conventionally known method. From the viewpoint of production efficiency, an in situ polymerization method or a phase separation method is preferred.

[0245] Hereinafter, a method for producing core-shell type colored resin particles by an in-situ polymerization method will be described.

[0246] Core-shell type colored resin particles can be obtained by adding a polymerizable monomer for forming a shell layer (polymerizable monomer for shell) and a polymerization initiator to an aqueous dispersion in which colored resin particles are dispersed and polymerizing the mixture.

[0247] As the polymerizable monomer for the shell, the same monomers as those mentioned above can be used. Among them, monomers that can give a polymer having a Tg of more than 80° C., such as styrene, acrylonitrile, and methyl methacrylate, are preferably used alone or in combination of two or more.

[0248] The addition amount of the polymerizable monomer for shell is not particularly limited, and relative to 100 parts by mass of the binding resin, as the lower limit, is preferably more than 1 part by mass, more preferably more than 2 parts by mass, and as the upper limit, is preferably less than 5 parts by mass, more preferably less than 4 parts by mass. In addition, the mass of the binding resin is the same as the mass of the polymerizable monomer for the core layer.

[0249] If the amount of the polymerizable monomer for shell added is above the lower limit, the heat resistance of the toner can be suppressed from decreasing, and the generation of fogging can be suppressed when the toner is stored for a long time in a high temperature and high humidity environment. If the amount of the polymerizable monomer for shell added is below the upper limit, the toner is easily diffused during fixing, so the reduction in print concentration can be suppressed. In addition, if the amount of the polymerizable monomer for shell added is within the above range, the storage stability and low temperature fixing property of the toner are improved.

[0250] Examples of the polymerization initiator used in the polymerization of the polymerizable monomer for the shell include metal persulfate salts such as potassium persulfate and ammonium persulfate, and water-soluble polymerization initiators such as azo initiators such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide) and 2,2'-azobis-(2-methyl-N-(1,1-bis(hydroxymethyl)2-hydroxyethyl)propionamide). These can be used alone or in combination of two or more.

[0251] The amount of the polymerization initiator is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, based on 100 parts by mass of the polymerizable monomer for the shell.

[0252] The polymerization temperature of the shell layer is not particularly limited, but is preferably 50° C. or higher, more preferably 60° C. or higher, from the viewpoint of rapidly advancing the polymerization reaction, and is preferably 95° C. or lower from the viewpoint of suppressing volatilization of the polymerizable monomer for the shell.

[0253] The reaction time for the polymerization of the shell layer is preferably 1 to 20 hours, more preferably 2 to 15 hours.

[0254] (A-4) Washing, filtration, dehydration and drying process

[0255] The aqueous dispersion of colored resin particles obtained by polymerization is preferably subjected to a series of operations of washing, filtering, dehydration, and drying repeatedly several times as necessary according to a conventional method after completion of the polymerization.

[0256] As the above-mentioned cleaning method, when an inorganic compound is used as a dispersion stabilizer, it is preferred to remove the dispersion stabilizer by adding an acid or an alkali to the aqueous dispersion of the colored resin particles so that the dispersion stabilizer is dissolved in water. When a colloid of an inorganic hydroxide that is poorly soluble in water is used as a dispersion stabilizer, it is preferred to add an acid to adjust the pH of the aqueous dispersion of the colored resin particles to 6.5 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used. Sulfuric acid is particularly preferred from the viewpoint of high removal efficiency and low burden on manufacturing equipment.

[0257] The dehydration and filtration methods can use various known methods, etc., and are not particularly limited. For example, centrifugal filtration, vacuum filtration, pressure filtration, etc. can be mentioned. In addition, the drying method is also not particularly limited, and various methods can be used.

[0258] (B) Crushing method

[0259] When the colored resin particles are produced by a pulverization method, the production can be carried out, for example, by the following process.

[0260] First, use a mixer, such as a ball mill, a V-type mixer, an FM Mixer (trade name: Japan Coking Industry Co., Ltd.), a high-speed dissolver, a Banbury mixer, a Forberg mixer, etc. to mix a binder resin, a colorant, a positively charged charge control resin, a polar resin, a release agent, and other additives such as a styrene-based thermoplastic elastomer added as needed. Then, use a pressure kneader, a double-shaft extrusion mixer, a roller, etc. to heat the mixture obtained above and mix it. Use a pulverizer such as a hammer mill, a cutting mill, and a roller mill to coarsely pulverize the resulting mixture. Then, after using a pulverizer such as a jet mill and a high-speed rotary pulverizer to perform fine pulverization, the desired particle size is classified by a classifier such as a wind classifier and an airflow classifier, so that colored resin particles can be obtained by a pulverization method.

[0261] In addition, the binder resin, colorant, positively charged charge control resin, polar resin, release agent and styrene-based thermoplastic elastomer used in the pulverization method can use the substances listed in the above-mentioned (A) suspension polymerization method. As the binder resin, in addition to the above-mentioned binder resins, resins such as polystyrene, polyester resins and epoxy resins that have been widely used in toners can also be used.

[0262] Furthermore, the colored resin particles obtained by the pulverization method can be converted into core-shell type colored resin particles by an in-situ polymerization method or the like, similarly to the colored resin particles obtained by the above-mentioned (A) suspension polymerization method.

[0263] 2. Colored resin particles

[0264] The colored resin particles can be obtained by a production method such as the above-mentioned (A) wet method such as the suspension polymerization method or (B) dry method such as the pulverization method.

[0265] The colored resin particles included in the toner are described below. The colored resin particles described below include both core-shell type particles and non-core-shell type particles.

[0266] The volume average particle size (Dv) of the colored resin particles is not particularly limited, but is preferably 3 to 15 μm, more preferably 4 to 12 μm. If Dv is within the above range, the possibility of reduced toner fluidity, deterioration of transferability, reduced image density, and reduced image resolution is small.

[0267] The ratio (Dv / Dn) of the volume average particle size (Dv) to the number average particle size (Dn) of the colored resin particles is preferably 1.0 to 1.3, more preferably 1.0 to 1.2. When Dv / Dn is within the above range, the transferability, image density, and resolution are less likely to be reduced.

[0268] The volume average particle size and number average particle size of the colored resin particles can be measured using, for example, a particle size analyzer (manufactured by Beckman Coulter, trade name: Multisizer) or the like.

[0269] From the viewpoint of image reproducibility, the average circularity of the colored resin particles is preferably from 0.96 to 1.00, more preferably from 0.97 to 1.00, and even more preferably from 0.98 to 1.00.

[0270] When the average circularity of the colored resin particles is within the above range, the printed thin line reproducibility is excellent.

[0271] 3. Toner

[0272] The toner of the present invention is obtained by mixing and stirring the colored resin particles obtained by the above method with an external additive and performing an external addition treatment. The toner of the present invention is formed by attaching an external additive to the surface of the colored resin particles and can be used as a single-component toner (developer). The single-component toner can also be further mixed and stirred with carrier particles to form a two-component developer.

[0273] As a method for external addition treatment for attaching the external additive to the surface of the colored resin particles, a known external addition treatment method can be adopted without particular limitation. For example, a mixer capable of mixing and stirring, such as FM Mixer (trade name: manufactured by Nippon Coking Industry Co., Ltd.), Super Mixer (trade name: manufactured by Kawada Seisakusho Co., Ltd.), Q Mixer (trade name: manufactured by Nippon Coking Industry Co., Ltd.), MecHanofusion System (trade name: manufactured by Hosokawa Micron Co., Ltd.), and MecHano Mill (trade name: manufactured by Okada Seiko Co., Ltd.), can be used to mix and stir the colored resin particles and the external additive, thereby performing external addition treatment.

[0274] As external additives, for example, inorganic particles such as silicon dioxide, titanium oxide, aluminum oxide, zinc oxide, tin oxide, strontium titanate, calcium carbonate, calcium phosphate or cerium oxide; organic particles such as polymethyl methacrylate resin, silicone resin or melamine resin; particles of metal soaps such as zinc stearate and magnesium stearate, etc. Among these, inorganic particles are preferred, and among inorganic particles, silicon dioxide particles and titanium oxide particles are preferred, and silicon dioxide particles are particularly preferred. These external additives can be used alone, or two or more kinds can be used in combination.

[0275] Furthermore, as the external additive, it is preferred that inorganic fine particles A having a number average primary particle size of 5 nm to 14 nm and inorganic fine particles B having a number average primary particle size of 15 nm to 90 nm are contained.

[0276] When the inorganic fine particles A and B are contained as external additives, the mass ratio of the inorganic fine particles A to B (inorganic fine particles A:inorganic fine particles B) is not particularly limited and may be, for example, 20:80 to 80:20.

[0277] In addition, the number average primary particle size of the external additive can be measured, for example, by weighing about 0.1 g of a measurement sample, taking it into a beaker, and adding 0.1 mL of an alkylbenzenesulfonic acid aqueous solution (manufactured by Fujifilm Corporation, trade name: DRIWEL) as a dispersant. 10 to 30 mL of a diluent (manufactured by Beckman Coulter, trade name: ISOTON II) is further added to the beaker, and dispersed for 3 minutes using a 20 W (watt) ultrasonic disperser, and then measured using a particle size measuring machine (manufactured by Beckman Coulter, trade name: Multisizer) under the conditions of an aperture of 100 μm, a medium of ISOTON II, and a number of particles to be measured of 100,000.

[0278] The content of the external additive is not particularly limited, but is preferably 0.05 to 6 parts by mass, more preferably 0.2 to 5 parts by mass, relative to 100 parts by mass of the colored resin particles. When the content of the external additive is within the above range, transfer residue and fogging are easily suppressed.

[0279] The toner of the present invention is a toner in which the release agent is not easily exuded even in a high temperature and high humidity environment. Therefore, after the toner of the present invention is stored in a high temperature and high humidity environment of 47°C and 80%RH for 30 days, the exudation rate calculated as the percentage of the number of exuded toner particles (B) relative to the total number of toner particles (A) can be less than 15%, in a more preferred embodiment, it can be less than 10%, and in a further preferred embodiment, it can be less than 5%. In addition, specifically, the exudation rate of the toner can be obtained by the same method as the evaluation of the exudation rate in the examples described later.

[0280] When the toner of the present invention is used, continuous printing can be performed using a cartridge filled with a large amount of toner in both a low-temperature and low-humidity environment and a high-temperature and high-humidity environment while suppressing the occurrence of printing defects until the amount of remaining toner decreases.

[0281] Therefore, when the colorant of the present invention is used to carry out a printing durability test in a high temperature and high humidity environment, the number of continuous prints that can maintain an image quality with a fog value of less than 2.0 can be made more than 10,000 sheets, in a more preferred embodiment, it can be made more than 15,000 sheets, and in a further preferred embodiment, it can be made greater than 20,000 sheets.

[0282] In addition, when 500 g of the colorant of the present invention is filled into an ink cartridge and a printing durability test is performed under a high temperature and high humidity environment, the amount of colorant that can maintain an image quality with a fog value of less than 2.0 can be set to a toner residual rate in the ink cartridge of less than 60%. In a more preferred embodiment, it can be set to a toner residual rate of less than 50%. In a further preferred embodiment, it can be set to a toner residual rate of less than 40%.

[0283] The toner remaining rate can be calculated using the following formula from the cartridge weight X (g) after continuous printing and the cartridge weight Y (g) before adding toner.

[0284]

[0285] The printing durability test and determination of the fog value under a high-temperature and high-humidity environment can be performed by the same method as the HH durability test in the examples described later.

[0286] In addition, when the colorant of the present invention is used to carry out a printing durability test in a low temperature and low humidity environment, the number of continuous prints that can maintain an image quality of a printing concentration (reflection concentration) of 1.3 or more can be made to be more than 10,000 sheets, in a more preferred embodiment, it can be made to be more than 15,000 sheets, and in a further preferred embodiment, it can be made to be greater than 20,000 sheets.

[0287] In addition, when 500 g of the colorant of the present invention is filled into an ink cartridge and a printing durability test is performed under a low temperature and low humidity environment, the amount of colorant that can maintain the image quality of a printing concentration of 1.3 or above can be set to a colorant residual rate in the ink cartridge of less than 60%. In a more preferred embodiment, it can be set to a colorant residual rate of less than 50%. In a further preferred embodiment, it can be set to a colorant residual rate of less than 40%.

[0288] The printing durability test and determination of the printing density in a low-temperature and low-humidity environment can be performed by the same method as the LL durability test in the examples described later.

[0289] The toner of the present invention is not prone to printing defects even when used after being stored for a long time in a high temperature and high humidity environment. Therefore, when the toner of the present invention is stored in a high temperature and high humidity environment at a temperature of 47° C. and a humidity of 80% RH for 30 days and subjected to a printing durability test in a high temperature and high humidity environment, the number of continuous prints that can maintain an image quality with a fog value of 2.0 or less can be 10,000 or more, in a more preferred embodiment, can be 15,000 or more, and in a further preferred embodiment, can be more than 20,000.

[0290] The colorant of the present invention can suppress the variation of the charge amount accompanying the change of temperature and humidity. Therefore, the difference (Q1-Q2) between the charge amount Q1 (μC / g) of the colorant when printing continuously up to 100 sheets in a low-temperature and low-humidity environment using the colorant of the present invention and the charge amount Q2 (μC / g) of the colorant when printing continuously up to 100 sheets in a high-temperature and high-humidity environment using the colorant of the present invention can be less than 25μC / g. In a more preferred embodiment, it can be less than 20μC / g. In a further preferred embodiment, it can be less than 15μC / g. In addition, continuous printing in a low-temperature and low-humidity environment or a high-temperature and high-humidity environment, and determination of the charge amounts Q1 and Q2 of the colorant can be carried out by the same method as the evaluation of the "charge variation caused by the environment" in the later-described embodiment.

[0291] 4. Image Formation Method

[0292] The toner of the present invention, when using an ink cartridge filled with a large amount of toner, can perform continuous printing in both a low-temperature and low-humidity environment and a high-temperature and high-humidity environment while suppressing the occurrence of printing defects until the amount of toner remaining decreases. Therefore, in an image forming method using the toner of the present invention, when using an ink cartridge filled with a large amount of toner, the effect brought about by the toner of the present invention can be effectively exerted.

[0293] In the image forming method of the present invention, the amount of toner filled in the ink cartridge is preferably 300 g or more, more preferably 400 g or more, and even more preferably 500 g or more. In addition, the amount of toner filled in the ink cartridge is usually 1000 g or less.

[0294] In addition, the image forming method of the present invention can set the amount of colorant used without causing impractical printing defects to a colorant residual rate in the ink cartridge of less than 60%. In a more preferred embodiment, it can be set to a colorant residual rate of less than 50%. In a further preferred embodiment, it can be set to a colorant residual rate of less than 40%.

[0295] The image forming method using the toner of the present invention can be a common image forming method, except for the toner filling amount and toner residual rate in the above-mentioned ink cartridge, and is not particularly limited. For example, an image forming method including a charging process, an exposure process, a developing process, a transfer process, a cleaning process, and a fixing process can be cited.

[0296] The charging process is a process of uniformly charging the surface of the photoreceptor with positive or negative charge by a charging member. Examples of charging methods of the charging member include a contact charging method using a charging roller, a brush, a magnetic brush, a scraper, etc., and a non-contact charging method using corona discharge.

[0297] The exposure process is a process of irradiating the photoreceptor surface with light corresponding to an image signal by an exposure device to form an electrostatic latent image on the uniformly charged photoreceptor surface. Examples of the exposure device include a laser irradiation device and an LED irradiation device.

[0298] The development process is a process in which a toner is attached to the electrostatic latent image formed on the surface of the photoreceptor by the exposure process by a developing device to form a visible image. In reversal development, the toner is attached only to the light-irradiated portion, and in regular development, the toner is attached only to the light-unirradiated portion.

[0299] The transfer process is a process of transferring the visible image on the surface of the photoreceptor formed by the developing device onto a recording material such as paper. The transfer is usually performed by a transfer roller, and other transfer methods include belt transfer and corona transfer.

[0300] The cleaning process is a process for cleaning the toner remaining on the surface of the photoreceptor after the transfer process. This is done by, for example, pressing a cleaning blade against the photoreceptor to scrape off the toner remaining on the surface of the photoreceptor. The scraped toner is usually recovered by a recovery device.

[0301] The fixing step is a step of fixing the visible image of the toner transferred to the recording material, and is performed by, for example, rotating at least one of a heat roller and a backup roller heated by a heating element, and applying heat and pressure while passing the recording material between them.

[0302] As fixing methods, heat, pressure, heat and pressure, solvent vapor, etc. are known. Among them, the heat and pressure method using the above-mentioned heat roller is the most widely used.

[0303] Example

[0304] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In addition, parts and % are by mass unless otherwise specified.

[0305] [Production Example 1: Synthesis of Polar Resin P1]

[0306] 200 parts of toluene were added to the reaction vessel, and the reaction vessel was fully replaced with nitrogen while stirring the toluene. Then, the toluene was heated to 90°C, and then a mixed solution of 97.0 parts of methyl methacrylate, 2.6 parts of ethyl acrylate, 0.4 parts of acrylic acid and 3 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) was added dropwise to the reaction vessel over 2 hours. Furthermore, the polymerization was completed by maintaining the toluene under reflux for 10 hours, and then the solvent was distilled off under reduced pressure. In this way, a polar resin P1 (MMA / EA / AA) was obtained. The acid value of the obtained polar resin P1 was 2.5 mgKOH / g, Tg was 74°C, and Mw was 12600.

[0307] [Production Example 2: Synthesis of Polar Resin P2]

[0308] Polar resin P2 (MMA / EA / AA) was obtained in the same manner as in Production Example 1 except that 97.3 parts of methyl methacrylate, 2.6 parts of ethyl acrylate and 0.1 parts of acrylic acid were used. The obtained polar resin P2 had an acid value of 0.5 mgKOH / g, a Tg of 74°C and an Mw of 12,500.

[0309] [Production Example 3: Synthesis of Polar Resin P3]

[0310] Polar resin P3 (MMA / EA / AA) was obtained in the same manner as in Preparation Example 1 except that 96.6 parts of methyl methacrylate, 2.6 parts of ethyl acrylate and 0.8 parts of acrylic acid were used. The obtained polar resin P3 had an acid value of 5.0 mgKOH / g, a Tg of 74°C and an Mw of 12,300.

[0311] [Production Example 4: Synthesis of Polar Resin P4]

[0312] Polar resin P4 (MMA / EA / AA) was obtained in the same manner as in Preparation Example 1 except that 95.9 parts of methyl methacrylate, 2.5 parts of ethyl acrylate and 1.6 parts of acrylic acid were used. The obtained polar resin P4 had an acid value of 10.0 mgKOH / g, a Tg of 74°C and an Mw of 12700.

[0313] [Production Example 5: Synthesis of SIS composition]

[0314] 23.2 kg of cyclohexane, 1.5 mmol of N,N,N',N'-tetramethylethylenediamine (TMEDA) and 1.70 kg of styrene were added to a pressure-resistant reactor and stirred at 40°C. At this time, 99.1 mmol of n-butyl lithium was added, and the resulting mixture was polymerized for 1 hour while heating to 50°C. The polymerization conversion rate of styrene was 100% by mass. Then, 6.03 kg of isoprene was continuously added to the reactor over a period of 1 hour while the temperature was controlled to maintain 50 to 60°C. After the addition of isoprene was completed, the polymerization was further performed for 1 hour to obtain a styrene-isoprene diblock copolymer (a) (copolymer (a) represented by Ar-D). The polymerization conversion rate of isoprene was 100% by mass. Next, 15.0 mmol of dimethyldichlorosilane as a coupling agent was added, and a coupling reaction was carried out for 2 hours to form a styrene-isoprene-styrene triblock copolymer (b) (copolymer (b) represented by Ar-D-Ar). After this, 198 mmol of methanol as a polymerization terminator was added, and the reaction was terminated by sufficient mixing, thereby obtaining a reaction solution containing a styrene-isoprene-styrene triblock copolymer (SIS) composition containing the above-mentioned block copolymers (a) and (b). A portion of the obtained reaction solution was taken out to determine the weight average molecular weight Mw of each block, the weight average molecular weight Mw of each block copolymer, the weight average molecular weight Mw of the entire SIS composition, the content ratio of each block copolymer, the styrene unit content, and the vinyl bond content of the conjugated diene block. The results obtained are shown in Table 1.

[0315] Then, 0.3 parts of 2,6-di-tert-butyl-p-cresol as an antioxidant was added to 100 parts (containing 30 parts of polymer components) of the reaction solution thus obtained and mixed, and the mixed solution was gradually dropped into warm water heated to 85-95°C in small amounts to volatilize the solvent to obtain a precipitate, which was crushed and dried with hot air at 85°C to recover the SIS composition. The melt index of the obtained SIS composition was measured. The obtained results are shown in Table 1. In addition, in Tables 3 to 5, the SIS composition is abbreviated as "SIS".

[0316] [Production Example 6: Synthesis of SBS composition]

[0317] In the above-mentioned Preparation Example 5, the addition amount of styrene was changed to 2.32 kg, and 5.41 kg of butadiene was used instead of 6.03 kg of isoprene. In the same manner as in the above-mentioned Preparation Example 5, a styrene-1,3-butadiene-styrene triblock copolymer (SBS) composition was obtained. In addition, in Tables 3 to 5, the SBS composition is abbreviated as "SBS".

[0318] [Table 1]

[0319]

[0320] [Example 1]

[0321] 1. Production of colored resin particles

[0322] 70 parts of styrene and 30 parts of n-butyl acrylate as monovinyl monomers, 9 parts of carbon black (Mitsubishi Chemical Corporation, trade name: #25B) as a black colorant, 0.7 parts of divinylbenzene as a crosslinkable polymerizable monomer, 1.0 parts of tert-dodecyl mercaptan as a molecular weight regulator, and 1.00 parts of polar resin P1 obtained in the above-mentioned manufacturing example 1 as a polar resin were mixed and wet-pulverized using a medium-type emulsifying disperser. Thereafter, 1.5 parts of CCR-A1 (copolymerization ratio of monomers containing quaternary ammonium salt groups: 2.00%), 1.0 parts of CCR-B1 (copolymerization ratio of monomers containing quaternary ammonium salt groups: 1.00%), 20 parts of behenyl stearate (molecular formula: C 200) as a release agent were further added. 17 H 35 -COO-C 22 H 45, melting point: 70° C., acid value: 0.1 mgKOH / g, hydroxyl value: 0.3 mgKOH / g, esterification rate: 98%), 5.0 parts of the SIS composition obtained in the above-mentioned Production Example 5 as a styrene-based thermoplastic elastomer, and mixed to obtain a polymerizable monomer composition.

[0323] Table 2 shows the monomer units and copolymerization ratios (mass %) constituting the CCR-A1 and the CCR-B1.

[0324] On the other hand, in a stirring tank, to an aqueous solution of 7.4 parts of magnesium chloride dissolved in 250 parts of ion-exchanged water, an aqueous solution of 4.1 parts of sodium hydroxide dissolved in 50 parts of ion-exchanged water was slowly added under stirring at room temperature to prepare a magnesium hydroxide colloidal dispersion (3.0 parts of magnesium hydroxide).

[0325] At room temperature, the above-mentioned polymerizable monomer composition was dropped into the magnesium hydroxide colloidal dispersion obtained above, and stirred until the droplets were stable. 5 parts of tert-butyl peroxide-2-ethylhexanoate (manufactured by NOF Corporation, trade name: Perbutyl O) as a polymerization initiator were added thereto, and then a pipeline emulsifying disperser (manufactured by Ohirayo Machinery Co., Ltd., trade name: Milder) was used to carry out high shear stirring at a speed of 15000 rpm to form droplets of the polymerizable monomer composition.

[0326] The suspension (polymerizable monomer composition dispersion) in which the droplets of the polymerizable monomer composition obtained above are dispersed is placed in a reactor equipped with a stirring blade, and the temperature is raised to 90°C to initiate a polymerization reaction. When the polymerization conversion rate reaches approximately 100%, 3.0 parts of methyl methacrylate as a polymerizable monomer for a shell is added to the reactor. Thereafter, the temperature is further maintained at 90°C for 3 hours to continue polymerization, and then the reaction is terminated by water cooling to obtain an aqueous dispersion of colored resin particles.

[0327] While stirring the aqueous dispersion of the colored resin particles obtained above at room temperature, sulfuric acid was added dropwise to perform acid washing until the pH became 6.5 or less. Then, filtration separation was performed, 500 parts of ion exchange water was added to the obtained solid component to make it re-slurry, and water washing treatment (washing, filtration and dehydration) was repeated several times. Then, filtration separation was performed, and the obtained solid component was placed in a container of a dryer and dried at 45° C. for 48 hours to obtain dried colored resin particles.

[0328] To 100 parts of the colored resin particles, 0.7 parts of silica fine particles A having a number average primary particle size of 10 nm and 1 part of silica fine particles B having a number average primary particle size of 55 nm after hydrophobization treatment with amino-modified silicone oil were added, and mixed using a high-speed stirrer (manufactured by Nippon Coking Industry Co., Ltd., trade name: FM Mixer) to perform external addition treatment to prepare the toner of Example 1.

[0329] [Examples 2 to 21 and Comparative Examples 1 to 8]

[0330] In Example 1, except that the materials added to the polymerizable monomer composition were changed according to Tables 3 to 5, the same procedure as in Example 1 was carried out to obtain toners of Examples 2 to 21 and Comparative Examples 1 to 8.

[0331] Table 2 shows the monomer units and copolymerization ratios (mass %) constituting the copolymers A, B, and C used in each of the Examples and Comparative Examples.

[0332] [Table 2]

[0333]

[0334] [evaluate]

[0335] The toners of the examples and comparative examples and the colored resin particles used in the toners were evaluated in detail as follows.

[0336] (1) Evaluation of colored resin particles

[0337] a. Volume average particle size (Dv), number average particle size (Dn) and particle size distribution (Dv / Dn)

[0338] About 0.1 g of the colored resin particles were weighed and placed in a beaker, and 0.1 mL of an aqueous surfactant solution (manufactured by Fujifilm Corporation, trade name: DRIWEL) as a dispersant was added. 10 to 30 mL of ISOTON II was further added to the beaker, and dispersed for 3 minutes using a 20 W ultrasonic disperser. The volume average particle size (Dv) and number average particle size (Dn) of the colored resin particles were measured using a particle size measuring machine (manufactured by Beckman Coulter, trade name: Multisizer) under the conditions of an aperture of 100 μm, a medium ISOTON II, and a number of particles to be measured of 100,000, and the particle size distribution (Dv / Dn) was calculated.

[0339] b. Average roundness

[0340] 10 mL of ion exchange water is added to the container in advance, 0.02 g of a surfactant as a dispersant is added thereto, and 0.02 g of colored resin particles are further added, and a dispersion treatment is performed at 60 W for 3 minutes using an ultrasonic disperser. The concentration of the colored resin particles during the measurement is adjusted to 3000 to 10000 particles / μL, and 5000 to 10000 colored resin particles with a circle equivalent diameter of 0.4 μm or more are measured using a flow particle image analyzer (manufactured by Sysmex Corporation, trade name: FPIA-3000). The average circularity is calculated from the measured value. The circularity is represented by the following calculation formula 1, and the average circularity is the value of the number average.

[0341] Calculation formula 1:

[0342]

[0343] (2) Toner Evaluation

[0344] a. Exudation rate

[0345] First, as the stored toner, a toner stored for 30 days in an environment of a temperature of 47° C. and a humidity of 80% RH is prepared.

[0346] The toner after storage is observed by SEM. 10 images of the toner are taken at a magnification of 2000 times. Then, for each taken toner image, the total number of toner particles (A) in the image and the number of toner particles (B) attached to the leaked release agent are counted. In addition, the toner particles attached to the leaked release agent are toner particles attached to the release agent with a maximum length greater than 0.3 μm that can be confirmed in the image. Thereafter, for each toner image, the number of toner particles (B) is divided by the number of toner particles (A), and the value multiplied by 100 is further calculated. The average of the values ​​calculated for the 10 toner images is taken as the seepage rate (%) of the toner. Based on the seepage rate, the effect of suppressing seepage is evaluated by the following evaluation criteria.

[0347] (Evaluation Criteria)

[0348] A: Less than 5%

[0349] B: 5% or more and less than 10%

[0350] C: 10% or more and less than 15%

[0351] D: 15% or more

[0352] b. Printing durability test under high temperature and high humidity environment (HH durability test)

[0353] In the printing durability test, a commercially available non-magnetic one-component developing type printer (printing speed: 40 sheets / minute for A4 size) was used. The printing durability test in a high temperature and high humidity environment was performed according to the following procedure.

[0354] First, 500 g of toner was placed in the toner cartridge of the developing device. After being placed in a high temperature and high humidity environment of 33.5°C and 82%RH for 24 hours, continuous printing was performed at a printing rate of 5% under the same environment until 20,000 sheets were printed. Five full-page prints (printing rate 100%) were performed for every 500 sheets, followed by full white printing (printing rate 0%). The printer was stopped in the middle of the full white printing, and the toner in the non-image area on the developed photoreceptor was attached to a tape (manufactured by Sumitomo 3M Co., Ltd., trade name: ScotchMending Tape 810-3-18) and adhered to the printed paper. Then, the whiteness (B) of the printed paper adhered with the tape was measured using a whiteness meter (manufactured by Nippon Denshoku Co., Ltd.). Similarly, only the unused tape was attached to the printed paper, and its whiteness (A) was measured. The difference in whiteness (BA) was taken as the fog value. The smaller the value, the less fog there is, and the better it is.

[0355] The number of continuous prints that can maintain image quality with a fog value of 2.0 or less was examined. Based on the number of continuous prints, the printing durability in a high-temperature and high-humidity environment was evaluated according to the following evaluation criteria.

[0356] (Evaluation Criteria)

[0357] A: More than 20,000 sheets

[0358] B: 15,000 or more and 20,000 or less

[0359] C: 10,000 or more and less than 15,000

[0360] D: Less than 10,000 sheets

[0361] The toner remaining rate is calculated by the following formula from the cartridge weight X (g) at the time when the image quality with a fog value of 2.0 or less cannot be maintained and the cartridge weight Y (g) before the toner is added.

[0362]

[0363] c. Printing durability test under low temperature and low humidity environment (LL durability test)

[0364] Using the same printing machine as in the above HH durability test, a printing durability test in a low temperature and low humidity environment was performed according to the following procedure.

[0365] First, 500 g of toner was placed in a toner cartridge of a developing device. After being placed in a low temperature and low humidity environment of 10°C and 20%RH for 24 hours, 20,000 sheets were continuously printed at a printing rate of 5% under the same environment. Five full-page printings (printing rate of 100%) were performed for every 500 sheets, and the printing density (reflection density) of the full-page printed portion was measured using a reflection image densitometer (manufactured by Macbeth, trade name: RD918).

[0366] The number of continuous prints that can maintain image quality at a print density of 1.3 or more was examined. Based on the number of continuous prints, the printing durability in a low-temperature and low-humidity environment was evaluated according to the following evaluation criteria.

[0367] (Evaluation Criteria)

[0368] A: More than 20,000 sheets

[0369] B: 15,000 or more and 20,000 or less

[0370] C: 10,000 or more and less than 15,000

[0371] D: Less than 10,000 sheets

[0372] The toner remaining rate is calculated in the same manner as above from the cartridge weight X (g) at the time when the image quality at a print density of 1.3 or more cannot be maintained and the cartridge weight Y (g) before the toner is added.

[0373] d. Printing durability test of toner after storage in a high temperature and high humidity environment (HH durability test after high temperature storage)

[0374] First, as a toner stored in a high temperature and high humidity environment, a toner stored in an environment of temperature 47°C and humidity 80% RH for 30 days was prepared. The toner after storage was used to perform a printing durability test under the same conditions as the above-mentioned HH durability test, and the number of continuous prints that can maintain an image quality with a fog value of 2.0 or less was studied. Based on the number of continuous prints, the printing durability of the toner stored in a high temperature and high humidity environment in a high temperature and high humidity environment was evaluated according to the following evaluation criteria.

[0375] (Evaluation Criteria)

[0376] A: More than 20,000 sheets

[0377] B: 15,000 or more and 20,000 or less

[0378] C: 10,000 or more and less than 15,000

[0379] D: Less than 10,000 sheets

[0380] e. Charge changes caused by the environment

[0381] Using the same printer as the HH durability test, toner was placed in the toner cartridge of the developing device, and after being placed in a low temperature and low humidity environment of 10°C and 20%RH for 24 hours, 100 sheets were continuously printed at a printing rate of 5% under the same environment. After printing 100 sheets, the toner carried on the developing roller was measured for the charge amount and the toner suction amount by an attraction type actual machine charge amount measuring device, and the value obtained by dividing the charge amount by the toner suction amount was taken as the toner charge amount Q1 (μC / g).

[0382] Likewise, the toner charge amount Q2 (μC / g) was measured under a high temperature and high humidity environment of a temperature of 33.5° C. and a humidity of 82% RH.

[0383] The difference (Q1-Q2) between Q1 and Q2 is calculated as an index of the charge change caused by the environment, and based on the value of the difference (Q1-Q2), the charge change caused by the environment is evaluated by the following evaluation criteria. In addition, the smaller the value of the difference between Q1 and Q2, the less the change in the charge amount of the toner caused by the change in temperature and humidity.

[0384] (Evaluation Criteria)

[0385] A: less than 15μC / g

[0386] B: 15μC / g or more and less than 20μC / g

[0387] C: 20μC / g or more and less than 25μC / g

[0388] D: 25μC / g or more

[0389] [Table 3]

[0390]

[0391] [Table 4]

[0392]

[0393] [Table 5]

[0394]

[0395] In Table 5, in Comparative Examples 2 and 3, |X×m P -F B ×m B | to replace |X×m P -F A ×m A|. In Comparative Example 7, F is calculated C -F B To replace F A -F B , calculate |X×m P -F C ×m C | to replace |X×m P -F A ×m A |.

[0396] [Research]

[0397] If any one of the copolymers A and B, which are positively chargeable charge control resins, and the polar resin is missing, it is difficult to suppress bleeding of the release agent while suppressing printing defects.

[0398] In Comparative Examples 1 and 6, since only the copolymer A was used as the positively charged charge control resin, when the toner was stored for 30 days in a high temperature and high humidity environment at a temperature of 47° C. and a humidity of 80% RH, the release agent easily oozes out, and fogging is easily generated in a printing durability test in a high temperature and high humidity environment using the stored toner. It is believed that in Comparative Examples 1 and 6, since only the copolymer A was used as the positively charged charge control resin, the amount of the copolymer A was adjusted so that the toner had an appropriate charge amount, and therefore the amount of the resin that was preferentially present on the surface of the colored resin particles became insufficient, and a dense resin layer was not formed.

[0399] In Comparative Examples 2 and 3, since only the copolymer B is used as the positively charged charge control resin, when the toner is stored for 30 days in a high temperature and high humidity environment of 47°C and 80%RH, the release agent is easily oozed, and fog is easily generated in the printing durability test under the high temperature and high humidity environment using the toner after storage, and further, fog is easily generated in the printing durability test under the high temperature and high humidity environment using the toner before storage. Since the copolymer B has a small amount of functional groups, it has a lower charge imparting effect than the copolymer A, and is not easy to be biased to the surface side of the colored resin particles. It can be considered that in Comparative Examples 2 and 3, since only the copolymer B is used as the positively charged charge control resin, the amount of resin biased to the surface of the colored resin particles becomes insufficient, a dense resin layer is not formed, and the charge amount of the toner is not sufficiently increased.

[0400] In Comparative Example 4, since no polar resin was used, when the toner was stored for 30 days in a high temperature and high humidity environment of 47°C and 80%RH, the release agent was easily exuded, and fogging was easily generated in the printing durability test in the high temperature and high humidity environment using the stored toner. Furthermore, the printing density was easily reduced in the printing durability test in the low temperature and low humidity environment using the toner before the storage. It can be inferred that in Comparative Example 4, since no polar resin was used, the amount of resin that was biased to the surface of the colored resin particles became insufficient, and a dense resin layer was not formed. In addition, the charge amount of the toner became too high.

[0401] In Comparative Example 5, since a polar resin having an acid value of more than 8.0 mgKOH / g is used, the charge amount of the toner changes greatly with changes in temperature and humidity, and fogging is easily generated in a printing durability test under a high-temperature and high-humidity environment. It can be inferred that the toner of Comparative Example 5 is prone to charge leakage due to moisture absorption of the acidic groups in a high-temperature and high-humidity environment because the polar resin has a large amount of acidic groups.

[0402] In Comparative Example 7, since a copolymer having a functional group content of more than 6.0% by mass was used instead of the copolymer A, the print density was easily reduced in the printing durability test under a low temperature and low humidity environment. It is considered that in Comparative Example 7, since the copolymer having a functional group content of more than 6.0% by mass was easily present on the surface of the colored resin particles, although a dense resin layer was formed, the charge amount of the toner became too high.

[0403] In Comparative Example 8, since a copolymer without a functional group was used instead of the copolymer B, when the toner was stored for 30 days in a high temperature and high humidity environment of 47°C and 80%RH, the release agent was easily oozed out, and fogging was easily generated in the printing durability test in a high temperature and high humidity environment using the stored toner. The copolymer without a functional group does not have a charge-imparting effect and is not easy to be present on the surface side of the colored resin particles. Therefore, it can be considered that in Comparative Example 8, since a copolymer without a functional group was used instead of the copolymer B, the amount of resin that was present on the surface of the colored resin particles became insufficient, and a dense resin layer was not formed.

[0404] In contrast, in each embodiment, as a positively charged charge control resin, a copolymer A having a functional group amount of 1.50 mass % or more and 6.00 mass % or less and a copolymer B having a functional group amount of 0.10 mass % or more and less than 1.50 mass % are used, and a polar resin having an acid value of 0.5 mgKOH / g or more and 5.0 mgKOH / g or less is further used. Therefore, even when the toner is stored for 30 days in a high temperature and high humidity environment at a temperature of 47°C and a humidity of 80%RH, the exudation of the release agent can be suppressed, and the generation of gray fog can be suppressed in a printing durability test under a high temperature and high humidity environment using the stored toner. In addition, in a printing durability test using an ink cartridge filled with 500g of toner, continuous printing can be performed under a low temperature and low humidity environment and a high temperature and high humidity environment while suppressing the occurrence of poor printing until the amount of toner remaining decreases. Furthermore, the change in the charge amount of the toner accompanying the change in temperature and humidity can be suppressed.

[0405] Furthermore, when comparing Examples 1, 16, and 17, Examples 1 and 17 using a monoester as a release agent can suppress the generation of fog under a high temperature and high humidity environment compared to Example 16 using a diester. This is presumably because the monoester has a greater effect of suppressing the aggregation of the toner under a high temperature and high humidity environment.

[0406] When comparing Example 1 and Example 17, Example 1 using behenyl behenate as a release agent can suppress the decrease in print density under a low-temperature and low-humidity environment compared to Example 17 using behenyl behenate as a release agent. It is inferred that behenyl stearate has a good effect of improving the low-temperature fixability of the toner, so the toner is easily melted and spread during fixing, thereby suppressing the decrease in print density.

[0407] When comparing Example 1 and Example 18, compared with Example 18 using the SBS composition as the styrene-based thermoplastic elastomer, Example 1 using the SIS composition as the styrene-based thermoplastic elastomer can suppress the bleeding of the release agent when the toner is stored under a high-temperature, high-humidity environment, and suppresses the generation of fog when the toner after storage is used under a high-temperature, high-humidity environment. It is inferred that this is because the use of the SIS composition improves the dispersibility of the release agent.

[0408] When comparing Example 1 and Example 19, Example 1 using core-shell type colored resin particles can suppress the occurrence of printing defects under high temperature and high humidity environments and low temperature and low humidity environments compared to Example 19 using colored resin particles without a shell. This is presumably because the shell suppresses the embedding of external additives in the printing durability test, thereby suppressing the change in charge amount caused by deterioration of the toner.

Claims

1. A toner comprising colored resin particles and an external additive, The colored resin particles contain a binder resin, a colorant, a positively charged charge control resin, and a release agent. The positively chargeable charge control resin comprises a copolymer A and a copolymer B, wherein the copolymer A comprises a functional group-containing monomer unit at a ratio of 1.50 mass % to 6.00 mass %, and the copolymer B comprises a functional group-containing monomer unit at a ratio of 0.10 mass % to less than 1.50 mass %. The colored resin particles further contain a polar resin having an acid value of 0.5 mgKOH / g or more and 8.0 mgKOH / g or less.

2. A toner comprising colored resin particles and an external additive, The colored resin particles contain a binder resin, a colorant, a positively charged charge control resin, and a release agent. The positively chargeable charge control resin comprises a copolymer A and a copolymer B, wherein the copolymer A comprises a functional group-containing monomer unit at a ratio of 1.50 mass % to 6.00 mass %, and the copolymer B comprises a functional group-containing monomer unit at a ratio of 0.10 mass % to less than 1.50 mass %. The colored resin particles further contain a polar resin having an acid value of 0.5 mgKOH / g or more and 5.0 mgKOH / g or less.

3. The toner according to claim 1 or 2, wherein In each copolymer contained in the positively charged charge control resin, when the proportion (mass %) of the functional group-containing monomer unit is F and the content (mass part) of the copolymer relative to 100 mass parts of the binder resin is m, the sum of the products of F and m (F×m) calculated for each copolymer is greater than 2.00 and less than 6.

00.

4. The toner according to claim 1 or 2, wherein When the acid value (mgKOH / g) of the polar resin is x and the content (parts by mass) of the polar resin relative to 100 parts by mass of the binder resin is m P The ratio (mass %) of the monomer units containing functional groups in the copolymer A is F A , the content (mass parts) of the copolymer A relative to 100 parts by mass of the binder resin is m A When X and m P The product of (X×m P ) and F A and m A The product of (F A ×m A ) is the absolute value of the difference (|X×m P -F A ×m A |) is below 2.

50.

5. The toner according to claim 1 or 2, wherein The release agent contains a fatty acid ester compound having a number average molecular weight (Mn) of 500 or more and less than 2000 in a ratio of 5 parts by mass to 30 parts by mass with respect to 100 parts by mass of the binder resin.

6. The toner according to claim 1 or 2, wherein The colored resin particles further contain a styrene-based thermoplastic elastomer in a ratio of 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the binder resin. 7 . An image forming method using the toner according to claim 1 .

Citation Information

Patent Citations

  • Toner for developing electrostatic images

    WO2014133032A1

  • Toner for developing electrostatic images

    WO2019065868A1

  • Electrostatic charge image development toner

    WO2020045664A1